Resin composition, cured film, insulating film or protective film, antenna element, and electronic component, display device or semiconductor device and method for manufacturing the same

By using a polyimide, polyamide, and polybenzoxazole resin composition with a specific structure, combined with alkali-soluble and photosensitive materials, the problems of reduced elongation and cracking in low-temperature cured films are solved, resulting in a highly reliable insulating and protective film suitable for semiconductor devices.

CN116323755BActive Publication Date: 2026-11-06TORAY INDUSTRIES INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202180068562.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-11-10
Filing Date
2021-10-18
Publication Date
2026-11-06
Estimated Expiration
2041-10-18

AI Technical Summary

Technical Problem

Existing polyimide and polybenzoxazole resins, after curing at low temperatures, exhibit reduced elongation of the cured film and are prone to cracking, failing to meet the packaging reliability requirements of next-generation memory such as MRAM.

Method used

A resin composition comprising polyimide, polyamide, polybenzoxazole or copolymer thereof containing a specific structure is used to form an insulating or protective film by curing at low temperature. This is combined with an alkali-soluble resin, a photosensitizer and a thermal crosslinking agent to form a cured film with high mechanical properties.

Benefits of technology

After curing at low temperatures, the cured film exhibits high elongation and crack resistance, meeting the requirements of packaging reliability testing, and is suitable for insulating and protective films for semiconductor devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
  • Figure QLYQS_3
    Figure QLYQS_3
Patent Text Reader

Abstract

The present application aims to provide a resin composition which does not show a decrease in elongation even after a package reliability test and has high crack resistance, a cured film, an insulating film or a protective film obtained from the resin composition, and an electronic component, a display device or a semiconductor device and a manufacturing method thereof. To solve the above problem, the resin composition of the present application contains (A) a resin and (E) a solvent, the aforementioned (A) resin contains at least one selected from the group consisting of polyimide, polyamide, polybenzoxazole, precursors thereof and copolymers thereof, and the aforementioned (A) resin has a structure represented by formula (1).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to resin compositions, cured films, insulating films or protective films, antenna elements, electronic components, display devices or semiconductor devices, and methods of manufacturing the same. Background Technology

[0002] In the past, polyimide resins and polybenzoxazole resins, which have excellent heat resistance and mechanical properties, have been widely used in the surface protective film and interlayer insulating film of semiconductor devices.

[0003] Typically, polyimide and polybenzoxazole are used to thermally dehydrate and ring-close their precursors in coatings, resulting in films with excellent heat resistance and mechanical properties. In this case, high-temperature calcination around 350°C is usually required. However, sealing resins, such as those used in next-generation memory devices like MRAM (Magnetoresistive Random Access Memory), are weak at high temperatures. Therefore, for surface protective films used in such devices, and for interlayer insulating films in fan-out wafer-level packages that form redistribution structures on sealing resins, calcination at low temperatures below approximately 250°C is required to obtain polyimide or polybenzoxazole resins with properties comparable to those obtained by calcining materials at high temperatures around 350°C in the past.

[0004] When resin compositions are used in applications such as semiconductors, the heat-cured film remains as a permanent film residue within the device; therefore, the physical properties of the cured film, especially its elongation, are very important. Furthermore, in applications such as insulating films between wiring layers in wafer-level packaging, the metal wiring undergoes repeated chemical treatments during formation, thus requiring chemical resistance to withstand these treatments.

[0005] To address these issues, a method has been proposed that uses a polybenzoxazole precursor with aliphatic groups (Patent Document 1) and a photosensitive resin composition containing a phenolic varnish resin with crosslinking groups (Patent Document 2). Existing technical documents Patent documents

[0006] Patent Document 1: Japanese Patent Application Publication No. 2008-224984 Patent Document 2: Japanese Patent Application Publication No. 2011-197362 Summary of the Invention The problem that the invention aims to solve

[0007] However, after the encapsulation reliability test, the cured films of the polybenzoxazole precursor with aliphatic groups described in Patent Document 1 and the photosensitive resin composition containing phenolic varnish resin described in Patent Document 2 showed deterioration of the resin contained in the cured film, with problems such as reduced elongation and cracking after the reliability test. Methods for solving problems

[0008] To address the aforementioned issues, the present invention relates to the following solution. Specifically, the resin composition of the present invention comprises (A) a resin and (E) a solvent, wherein the aforementioned (A) resin comprises at least one selected from polyimide, polyamide, polybenzoxazole, their precursors, and their copolymers, and the aforementioned (A) resin has the structure shown in formula (1).

[0009] [Chemistry 1]

[0010] In equation (1), a is an independent integer from 0 to 4, b is an independent integer from 0 to 2, and when b is 0, the part in parentheses represents a single bond, and n is an integer from 1 to 12. A is an independent single bond, -O-, -S-, -CO-, -COO-, -OCO-, -NHCO-, -CONH-, or a divalent hydrocarbon group with 1 to 5 carbon atoms, R 1 Each of these can be independently represented by a halogen atom, a hydroxyl group, a monovalent hydrocarbon group with 1 to 6 carbon atoms, an alkoxy group with 1 to 6 carbon atoms, or a phenoxy group. * indicates a chemical bond.

[0011] The first method of obtaining the cured film of the present invention is to cure the resin composition of the present invention.

[0012] The second aspect of the cured film of the present invention is a cured film having a resin (A), wherein the resin (A) comprises at least one selected from polyimide, polyamide, polybenzoxazole, their precursors and their copolymers, and the resin (A) has the structure shown in formula (1).

[0013] The insulating film or protective film of the present invention has the cured film of the present invention.

[0014] The method for manufacturing an electronic component, display device, or semiconductor device of the present invention includes the steps of: coating a resin composition of the present invention and drying it to form a resin film; irradiating the resin film with chemical rays; developing the resin film to form a pattern; and performing heat treatment to form a textured pattern layer of a cured film.

[0015] A first aspect of the electronic component, display device, or semiconductor device of the present invention has a textured layer of the cured film of the present invention.

[0016] In a second embodiment of the electronic component, display device, or semiconductor device of the present invention, the cured film of the present invention is configured as an insulating film between wirings.

[0017] The antenna element of the present invention has at least one antenna wiring and the curing film of the present invention. The antenna wiring includes at least one selected from bent loop antennas, coil loop antennas, bent monopole antennas, bent dipole antennas, and microstrip antennas. The proprietary area of ​​an average antenna portion in the antenna wiring is 1000 mm². 2 The cured film is described below as an insulating film that insulates the ground wire from the antenna wiring. The effects of the invention

[0018] The invention provides a resin composition that does not show a decrease in elongation after packaging reliability testing and has high crack resistance; a cured film, insulating film or protective film obtained from the resin composition; and electronic components, display devices or semiconductor devices and methods for manufacturing the same. Attached Figure Description

[0019] Figure 1 This is a schematic diagram of an example of a coplanar powered microstrip antenna, which is a type of planar antenna. Figure 2 This is a schematic cross-sectional view of an example of a semiconductor package having an IC chip (semiconductor element), a redistribution layer, a sealing resin, and an antenna element. Detailed Implementation

[0020] The present invention will be described in detail below.

[0021] The resin composition of the present invention contains (A) resin and (E) solvent, wherein the aforementioned (A) resin comprises at least one selected from polyimide, polyamide, polybenzoxazole, their precursors and their copolymers, and the aforementioned (A) resin has the structure shown in formula (1).

[0022] [Chemistry 2]

[0023] In equation (1), a is an independent integer from 0 to 4, b is an independent integer from 0 to 2, and when b is 0, the part in parentheses represents a single bond, and n is an integer from 1 to 12. A is an independent single bond, -O-, -S-, -CO-, -COO-, -OCO-, -NHCO-, -CONH-, or a divalent hydrocarbon group with 1 to 5 carbon atoms, R 1 Each of these can be independently represented by a halogen atom, a hydroxyl group, a monovalent hydrocarbon group with 1 to 6 carbon atoms, an alkoxy group with 1 to 6 carbon atoms, or a phenoxy group. * indicates a chemical bond. <(A) Resin> The resin composition of the present invention contains (A) resin (hereinafter sometimes referred to as component (A)). Resin (A) comprises at least one selected from polyimide, polyamide, polybenzoxazole, precursors thereof, and copolymers thereof. In the present invention, "copolymers thereof" refers to copolymers obtained by copolymerizing two or more selected from polyimide, polyamide, polybenzoxazole, and precursors thereof.

[0024] This document describes polyimides, polyamides, polyimide precursors, polybenzoxazoles, and polybenzoxazole precursors. Polyimides are not particularly limited as long as they contain an imide ring. Furthermore, polyimide precursors are not particularly limited as long as they have a structure that forms a polyimide with an imide ring through dehydration and ring closure, and may contain polyamic acid, polyamic ester, etc. Polyamides are not particularly limited as long as they contain an amide bond. Polybenzoxazoles are not particularly limited as long as they contain a benzoxazole ring. Polybenzoxazole precursors are not particularly limited as long as they have a structure that forms a polybenzoxazole with a benzoxazole ring through dehydration and ring closure, and may contain polyhydroxyamides, etc.

[0025] From the viewpoint that the resin can easily obtain excellent properties as a surface protective film for semiconductor elements, an interlayer insulating film, an insulating layer for display devices such as organic light-emitting elements, and a planarization film for TFT substrates, it is preferable that the amount of gas emitted at high temperatures of 160°C or higher after heat treatment is low. Specifically, the resin in (A) preferably contains at least one selected from polyimide, polybenzoxazole, their precursors and copolymers.

[0026] (A) The resin has the structure shown in formula (1).

[0027] [Chemistry 3]

[0028] In equation (1), a is an independent integer from 0 to 4, b is an independent integer from 0 to 2, and when b is 0, the part in parentheses represents a single bond, and n is an integer from 1 to 12. A is an independent single bond, -O-, -S-, -CO-, -COO-, -OCO-, -NHCO-, -CONH-, or a divalent hydrocarbon group with 1 to 5 carbon atoms, R 1 Each atom is independently a halogen atom, a hydroxyl group, a monovalent hydrocarbon group with 1 to 6 carbon atoms, an alkoxy group with 1 to 6 carbon atoms, or a phenoxy group. * indicates a chemical bond. From the viewpoint of solvent solubility, it is preferable that each a is an independent integer from 1 to 4. From the viewpoint of heat resistance, A is preferably a single bond, -O-, -S-, -CO-, -COO-, -OCO-, -NHCO-, or -CONH-. From the viewpoint of high elongation, n is preferably 4 or more, more preferably 6 or more.

[0029] As a method for obtaining resin (A), examples include polycondensation of dicarboxylic acids, dicarboxylic acid derivatives, dianhydrides, diamines, diisocyanates, etc., having the structure shown in formula (1). Specific examples of dicarboxylic acid derivatives having the structure shown in formula (1) include active amide compounds such as dicarboxylic acid dichlorohydrin, hydroxybenzotriazole, and imidazole, but are not limited to these. From the viewpoint of being able to polymerize under mild conditions, when obtaining resin (A) having the structure shown in formula (1) by polycondensation, diamines having the structure shown in formula (1) are preferred.

[0030] In a first suitable manner, the resin composition of the present invention preferably comprises (A) a alkali-soluble resin, further containing (B-1) a compound that generates acid upon light (hereinafter sometimes referred to as component (B-1)) and (C-1) a thermal crosslinking agent (hereinafter sometimes referred to as component (C-1)). By containing component (B-1), the resin composition can be imparted with photosensitivity. By imparting component (C-1), the mechanical properties of the cured film can be improved. By imparting photosensitivity, the processing steps for forming through-holes in interlayer insulating films, etc., can be streamlined.

[0031] (A) The resin is an (a-1) alkali-soluble resin, which easily reduces environmental impact. The alkali solubility of the resin in this invention will be explained. A solution obtained by dissolving the resin in γ-butyrolactone is coated onto a silicon wafer and pre-baked at 120°C for 4 minutes to form a pre-baked film with a thickness of 10 μm ± 0.5 μm. Next, the pre-baked film is immersed for 1 minute in an alkaline aqueous solution selected from any one of a 2.38% by mass tetramethylammonium hydroxide aqueous solution, a 1% by mass potassium hydroxide aqueous solution, or a 1% by mass sodium hydroxide aqueous solution at 23 ± 1°C, and the reduction in film thickness when rinsed with pure water is measured. A resin with a dissolution rate of 50 nm / min or higher for the above pre-baked film is defined as alkali-soluble.

[0032] Furthermore, a second suitable embodiment of the resin composition of the present invention preferably further contains (B-2) a photopolymerization initiator (hereinafter sometimes referred to as (B-2) component) and (C-2) a compound having two or more olefinic unsaturated bonds (hereinafter sometimes referred to as (C-2) component). By containing (B-2) component and (C-2) component, the resin composition can be endowed with photosensitivity.

[0033] Furthermore, a third suitable embodiment of the resin composition of the present invention preferably further contains a (B-2) photopolymerization initiator, wherein the (A) resin preferably has olefinically unsaturated bonds. By containing the (A) resin having olefinically unsaturated bonds and the (B-2) component, the resin composition can be endowed with photosensitivity.

[0034] One method for introducing organic groups having olefinic unsaturated bonds is, for example, reacting a tetracarboxylic dianhydride with an alcohol having olefinic unsaturated bonds to generate a tetracarboxylic acid diester, followed by an amide polycondensation reaction of the diester with a polyamine compound. Another method is, for example, reacting trifluoroacetic acid and an alcohol having olefinic unsaturated bonds with a polyamic acid obtained from an olefinic dianhydride and a diamine.

[0035] As a method for generating the aforementioned tetracarboxylic acid diester, the aforementioned acid dianhydride and alcohol can also be reacted directly in a solvent; however, from a reactivity point of view, it is preferable to use a reaction activator. Examples of reaction activators include tertiary amines such as pyridine, dimethylaminopyridine, triethylamine, N-methylmorpholine, and 1,8-diazabicycloundecene. The amount of reaction activator added is preferably 3 moles or more and 300 moles or less, more preferably 20 moles or more and 150 moles or less, relative to 100 moles of the reacting acid anhydride group.

[0036] Examples of alcohols containing olefinic unsaturated bonds include alcohols having one olefinic unsaturated bond and one hydroxyl group, and alcohols having two or more olefinic unsaturated bonds and one hydroxyl group.

[0037] Examples of alcohols having one olefinic unsaturated bond and one hydroxyl group include 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, 2-hydroxybutyl methacrylate, 1-(meth)acryloyloxy-2-propanol, 2-(meth)acrylamide ethanol, hydroxymethyl vinyl ketone, 2-hydroxyethyl vinyl ketone, 2-hydroxy-3-methoxypropyl methacrylate, 2-hydroxy-3-butoxypropyl methacrylate, 2-hydroxy-3-phenoxypropyl methacrylate, 2-hydroxy-3-tert-butoxypropyl methacrylate, 2-hydroxy-3-cyclohexylalkoxypropyl methacrylate, 2-hydroxy-3-cyclohexyloxypropyl methacrylate, and 2-(meth)acryloyloxyethyl-2-hydroxypropyl phthalate.

[0038] Examples of alcohols having two or more olefinic unsaturated bonds and one hydroxyl group include glycerol-1,3-di(meth)acrylate, glycerol-1,2-di(meth)acrylate, trimethylolpropane di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol penta(meth)acrylate, glycerol-1-allyloxy-3-methacrylate, glycerol-1-allyloxy-2-methacrylate, 2-ethyl-2-(hydroxymethyl)propane-1,3-diylbis(2-methacrylate), and 2-(acryloyloxy)-2-(hydroxymethyl)butyl methacrylate. It should be noted that in this invention, "(meth)acrylate" refers to methacrylate or acrylate. The same applies to similar expressions.

[0039] When reacting acid anhydrides with alcohols containing olefinic unsaturated bonds, other alcohols may also be used simultaneously. These other alcohols can be appropriately selected for various purposes, such as adjusting exposure sensitivity or solubility in organic solvents. Specifically, examples include aliphatic alcohols and monoalcohols derived from oxidized alkenes. Examples of aliphatic alcohols include methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, isobutanol, tert-butanol, 1-pentanol, 2-pentanol, 3-pentanol, and isopentanol. Examples of monools derived from olefin oxides include ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, triethylene glycol monomethyl ether, triethylene glycol monoethyl ether, triethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monobutyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol monobutyl ether, tripropylene glycol monomethyl ether, tripropylene glycol monoethyl ether, and tripropylene glycol monobutyl ether.

[0040] Furthermore, as a method for introducing organic groups having olefinic unsaturated bonds, ionic bonds can be used. Examples of methods for introducing organic groups having olefinic unsaturated bonds using ionic bonds include reacting polyamic acid obtained by reacting an acid dianhydride with a diamine, and reacting a tertiary amine having olefinic unsaturated bonds. Examples of tertiary amines having olefinic unsaturated bonds include compounds represented by formula (8).

[0041] [Chemistry 4]

[0042] In equation (8), R 20 Represents a hydrogen atom or a methyl group. R 21 and R 22 Each of the following can be independently represented as methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, tert-butyl, or phenyl. Z represents an integer from 1 to 10.

[0043] Among the compounds shown in formula (8), dimethylaminoethyl methacrylate, diethylaminoethyl methacrylate, dimethylaminopropyl methacrylate, and diethylaminopropyl methacrylate are preferred as they tend to improve exposure sensitivity.

[0044] Furthermore, as other methods for introducing organic groups having olefinic unsaturated bonds, examples include reacting hydroxyl and / or carboxyl groups in a resin with compounds having olefinic unsaturated double bond groups; and polymerizing monomers having olefinic unsaturated bonds to obtain resins. From a reactivity point of view, electrophilic compounds having olefinic unsaturated double bond groups are preferred as compounds having olefinic unsaturated double bond groups.

[0045] Examples of electrophilic compounds include isocyanate compounds, isothiocyanate compounds, epoxy compounds, aldehyde compounds, thioaldehyde compounds, ketone compounds, thioketone compounds, acetate compounds, carboxylic acid acyl chlorides, carboxylic acid anhydrides, reactive carboxylic acid ester compounds, carboxylic acid compounds, haloalkyl compounds, azidoalkyl compounds, trifluoromethanesulfonate alkyl compounds, methanesulfonate alkyl compounds, p-toluenesulfonate alkyl compounds, and cyanide alkyl compounds. From the viewpoint of reactivity and compound usability, isocyanate compounds, epoxy compounds, aldehyde compounds, ketone compounds, and carboxylic acid anhydrides are preferred, and isocyanate compounds, epoxy compounds, and carboxylic acid anhydrides are more preferred.

[0046] The resin composition of the present invention may contain a polymerization inhibitor. By containing a polymerization inhibitor, cross-linking at the olefin unsaturated bond sites during the reaction can be easily prevented. Examples of polymerization inhibitors include hydroquinone, 4-methoxyphenol, tert-butylpyrocatechol, and bis-tert-butylhydroxytoluene, among other phenolic compounds. The content of the polymerization inhibitor is preferably 0.1 moles or more and 5 moles or less of the phenolic hydroxyl groups relative to 100 moles of the olefin unsaturated bond in the alcohol.

[0047] From the perspective of improving alkali solubility, in the aforementioned formula (1), b is preferably an integer from 1 to 2, and R 1 One or two of them are hydroxyl groups.

[0048] Furthermore, from the perspective of heat resistance, in the aforementioned formula (1), b is preferably 1.

[0049] Furthermore, it is preferred that (A) resin has one or more structural units selected from the structural units shown in formula (2), formula (3), and formula (4).

[0050] [Chemistry 5]

[0051] In equation (2), R 2 This refers to a tetravalent organic group having 4 to 40 carbon atoms. Examples of tetravalent organic groups having 4 to 40 carbon atoms include structures obtained by removing a carboxyl group from an aromatic tetracarboxylic acid and structures obtained by removing a carboxyl group from an aliphatic tetracarboxylic acid. Aliphatic tetracarboxylic acids preferably include alicyclic tetracarboxylic acids.

[0052] Specific examples of aromatic tetracarboxylic acids include pyromellitic acid, 3,3′,4,4′-biphenyltetracarboxylic acid, 2,3,3′,4′-biphenyltetracarboxylic acid, 2,2′,3,3′-biphenyltetracarboxylic acid, 3,3′,4,4′-diphenyl ether tetracarboxylic acid, 3,3′,4,4′-benzophenone tetracarboxylic acid, 2,2′,3,3′-benzophenone tetracarboxylic acid, 2,2-bis(3,4-dicarboxyphenyl)propane, 2,2-bis(2,3-dicarboxyphenyl)propane, 1,1-bis(3,4-dicarboxyphenyl)ethane, and 1,1-bis(2 Examples of aliphatic tetracarboxylic acids include 3,4-dicarboxyphenyl)ethane, bis(3,4-dicarboxyphenyl)methane, bis(2,3-dicarboxyphenyl)methane, bis(3,4-dicarboxyphenyl) ether, 1,2,5,6-naphthalenetetracarboxylic acid, 9,9-bis(3,4-dicarboxyphenyl)fluorene, 9,9-bis{4-(3,4-dicarboxyphenoxy)phenyl}fluorene, 2,3,6,7-naphthalenetetracarboxylic acid, 2,3,6,7-naphthalenetetracarboxylic acid, 2,3,5,6-pyridinetetracarboxylic acid, 3,4,9,10-perylenetetracarboxylic acid, and 2,2-bis(3,4-dicarboxyphenyl)hexafluoropropane. Specific examples of aliphatic tetracarboxylic acids include cyclobutanetetracarboxylic acid and 1,2,3,4-cyclopentanetetracarboxylic acid. Preferably, the compounds are pyromellitic tetracarboxylic acid, 3,3′,4,4′-biphenyltetracarboxylic acid, 3,3′,4,4′-diphenyl ether tetracarboxylic acid, and 2,2-bis(3,4-dicarboxyphenyl)hexafluoropropane. The compounds may contain two or more structures obtained by removing the carboxyl group from these tetracarboxylic acids.

[0053] R 3 The structural unit represents the case where b is 1 or 2 in the structure shown in the aforementioned equation (1).

[0054] [Chemistry 6]

[0055] In equation (3), R 4 R represents an organic group with 4 to 40 carbon atoms and a 2 to 8 valence. 5 R represents the structural unit in the structure shown in equation (1) above, where b is 1 or 2. 6 This represents a monovalent hydrocarbon group with 1 to 20 hydrogen or carbon atoms. q and r represent integers within the range of 0 ≤ q ≤ 4 and 0 ≤ r ≤ 4, respectively. When q and r are 0, (OH) q (COOR) 6 ) rThis represents a hydrogen atom. q and r represent integers that satisfy 0 ≤ q + r ≤ 6.

[0056] [Chemistry 7]

[0057] In equation (4), R 7 R represents the structural unit in the structure shown in equation (1) above where b is 0. 8 It represents a divalent organic group with 4 to 40 carbon atoms.

[0058] R 4 R 8 A structure obtained by removing the portion originating from two carboxyl groups from a structure obtained by condensing a carboxylic acid having two or more carboxyl groups. R 4 Further steps are taken, involving 0–6 hydrogen atoms with OH and / or COOR. 6 The resulting structure is replaced, forming 2- to 8-valent groups.

[0059] Examples of carboxylic acids having two or more carboxyl groups include aromatic dicarboxylic acids, aromatic tricarboxylic acids, aromatic tetracarboxylic acids, alicyclic dicarboxylic acids, and aliphatic tetracarboxylic acids.

[0060] Examples of aromatic dicarboxylic acids include terephthalic acid, isophthalic acid, diphenyl ether dicarboxylic acid, bis(carboxyphenyl)hexafluoropropane, biphenyl dicarboxylic acid, benzophenone dicarboxylic acid, and triphenyl dicarboxylic acid.

[0061] Examples of aromatic tricarboxylic acids include trimellitic acid, pyromellitic acid, diphenyl ether tricarboxylic acid, and biphenyl tricarboxylic acid.

[0062] Examples of aromatic tetracarboxylic acids include pyromellitic acid, 3,3′,4,4′-biphenyltetracarboxylic acid, 2,3,3′,4′-biphenyltetracarboxylic acid, 2,2′,3,3′-biphenyltetracarboxylic acid, 3,3′,4,4′-diphenyl ether tetracarboxylic acid, 3,3′,4,4′-benzophenone tetracarboxylic acid, 2,2′,3,3′-benzophenone tetracarboxylic acid, 2,2-bis(3,4-dicarboxyphenyl)propane, 2,2-bis(2,3-dicarboxyphenyl)propane, 1,1-bis(3,4-dicarboxyphenyl)ethane, and 1,1-bis(2,3... Di(3,4-dicarboxyphenyl)ethane, bis(2,3-dicarboxyphenyl)methane, bis(3,4-dicarboxyphenyl) ether, 1,2,5,6-naphthalenetetracarboxylic acid, 9,9-bis(3,4-dicarboxyphenyl)fluorene, 9,9-bis{4-(3,4-dicarboxyphenoxy)phenyl}fluorene, 2,3,6,7-naphthalenetetracarboxylic acid, 2,3,6,7-naphthalenetetracarboxylic acid, 2,3,5,6-pyridinetetracarboxylic acid, 3,4,9,10-perylenetetracarboxylic acid, 2,2-bis(3,4-dicarboxyphenyl)hexafluoropropane, etc.

[0063] Examples of alicyclic dicarboxylic acids include 1,4-cyclohexanedicarboxylic acid.

[0064] Examples of aliphatic tetracarboxylic acids include cyclobutanetetracarboxylic acid and 1,2,3,4-cyclopentanetetracarboxylic acid.

[0065] Preferably, the following are selected: diphenyl ether dicarboxylic acid, bis(carboxyphenyl)hexafluoropropane, pyromellitic acid, 3,3′,4,4′-biphenyltetracarboxylic acid, 3,3′,4,4′-diphenyl ether tetracarboxylic acid, and 2,2-bis(3,4-dicarboxyphenyl)hexafluoropropane. 4 R 8 It may include two or more structures obtained by removing portions derived from two carboxyl groups from structures obtained by condensing these carboxylic acids having two or more carboxyl groups.

[0066] Resin (A) containing the structural unit shown in formula (1) of formula (2), formula (3) or formula (4) is unlikely to cause high elongation in the cured film of the resin composition, and the elongation after reliability test is reduced, and high crack resistance is easily obtained.

[0067] The structural unit shown in formula (3) has a carboxyl group or carboxyl ester group at the ortho position of the aromatic amide group, which can form an imide ring structure, for example, through dehydration and ring closure. Furthermore, in the case of the polybenzoxazole precursor, R in formula (3) 5 Having an aromatic group and a hydroxyl group ortho to the aromatic amide group, it can form a benzoxazole ring structure, for example, by dehydration and ring closure.

[0068] Furthermore, the total content of the structural units shown in formula (2), formula (3), and formula (4) in the total structural units of (A) resin is preferably 10 mol% or more and 80 mol% or less, more preferably 30 mol% or more and 80 mol% or less, and most preferably 50 mol% or more and 80 mol% or less. By satisfying these requirements, it is easy to impart high elongation to the cured film.

[0069] Furthermore, from the viewpoint of alkali solubility, R in the aforementioned formula (1) is preferred. 1 Each of the structural units is independently a halogen atom, a monovalent hydrocarbon group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, or a phenoxy group. The total content of the structural units shown in formula (2), formula (3), and formula (4) is more than 10 mol% and less than 20 mol% in 100 mol% of the total structural units of (A) resin.

[0070] Furthermore, in the aforementioned equation (1), a is an integer from 1 to 4, and R... 1One or two of them are hydroxyl groups. The total content of the structural units shown in formula (2), formula (3), and formula (4) in the total structural units of (A) resin is preferably 10 mol% or more and 100 mol% or less, more preferably 50 mol% or more and 100 mol% or less, and most preferably 80 mol% or more and 100 mol% or less. By satisfying the above requirements, the resin composition is made easy to impart high elongation to the cured film while ensuring alkali solubility.

[0071] (A) The resin can be dehydrated and cyclically closed to form polyimide or polybenzoxazole, or it can be used as a precursor in the form of polyamide, without necessarily requiring dehydration and cyclic closure.

[0072] R 3 R 5 R 7 It can be obtained from diamine residues having the structure shown in formula (1), or it can be obtained by copolymerizing structural units obtained from diamine residues other than the diamine having the structure shown in formula (1). Specific examples of diamines constituting diamine residues other than the diamine having the structure shown in formula (1) include 3,4′-diaminodiphenyl ether, 4,4′-diaminodiphenyl ether, 3,4′-diaminodiphenylmethane, 4,4′-diaminodiphenylmethane, 1,4-bis(4-aminophenoxy)benzene, benzidine, m-phenylenediamine, p-phenylenediamine, 1,5-naphthylenediamine, 2,6-naphthylenediamine, bis(4-aminophenoxy)biphenyl, bis{4-(4-aminophenoxy)phenyl} ether, 1,4-bis(4-aminophenoxy)benzene, 2,2′-dimethyl-4,4′-diaminobiphenyl, 2,2′- Compounds obtained by substituting at least a portion of the hydrogen atoms of the aromatic rings of diethyl-4,4′-diaminobiphenyl, 3,3′-dimethyl-4,4′-diaminobiphenyl, 3,3′-diethyl-4,4′-diaminobiphenyl, 2,2′,3,3′-tetramethyl-4,4′-diaminobiphenyl, 3,3′,4,4′-tetramethyl-4,4′-diaminobiphenyl, 2,2′-bis(trifluoromethyl)-4,4′-diaminobiphenyl, 9,9-bis(4-aminophenyl)fluorene, or compounds obtained by substituting at least a portion of the hydrogen atoms of these aromatic rings with alkyl or halogen atoms; aliphatic cyclohexyldiamines, methylene dicyclohexylamines, and diamines having the structures shown below. Two or more of these may be used.

[0073] [Chemistry 8]

[0074] [Chemistry 9]

[0075] Furthermore, aliphatic groups having a siloxane structure can be copolymerized without reducing heat resistance. Copolymerizing these groups improves adhesion to the substrate. Specifically, examples of diamine components include copolymerizing 1 to 15 mol% of diamine components such as bis(3-aminopropyl)tetramethyldisiloxane and bis(p-aminophenyl)octamethylpentasiloxane. Copolymerization of 1 mol% or more is preferred in terms of improved adhesion to substrates such as silicon wafers. Furthermore, copolymerization of 15 mol% or less is preferred in terms of reducing solubility in alkaline solutions.

[0076] (A) The resin preferably has the structure shown in formula (6) and / or the structure shown in formula (7). By having the aforementioned structure, it is easy to reduce the rate of change of elongation at break after reliability testing.

[0077] [Chemistry 10]

[0078] In equation (6), R 16 and R 17 Each represents a monovalent organic group or hydroxyl group with 1 to 5 carbon atoms, v and w represent integers from 0 to 4, m represents integers from 0 to 2, and * represents a chemical bond. Except for those included in the structural unit shown in formula (1).

[0079] [Chemistry 11]

[0080] In equation (7), R 18 and R 19 Each represents a monovalent organic group or hydroxyl group with 1 to 5 carbon atoms, x and y represent integers from 0 to 4, and * represents a chemical bond.

[0081] As diamine components having the structure shown in formula (6) and / or the structure shown in formula (7), examples include m-phenylenediamine, p-phenylenediamine, 1,5-naphthylenediamine, 2,6-naphthylenediamine, benzidine, 3,3′-dihydroxybenzidine, bis(4-aminophenoxy)biphenyl, 2,2′-dimethyl-4,4′-diaminobiphenyl, 2,2′-diethyl-4,4′-diaminobiphenyl, 3,3′-dimethyl-4,4′- Diaminobiphenyl, 3,3′-diethyl-4,4′-diaminobiphenyl, 2,2′,3,3′-tetramethyl-4,4′-diaminobiphenyl, 3,3′,4,4′-tetramethyl-4,4′-diaminobiphenyl, 2,2′-bis(trifluoromethyl)-4,4′-diaminobiphenyl, 4,4″-diamino-p-terphenyl, or compounds obtained by substituting at least some of the hydrogen atoms of these aromatic rings with alkyl or halogen atoms, etc.

[0082] Examples of dicarboxylic acids having the structure shown in formula (6) and / or formula (7) include terephthalic acid, isophthalic acid, biphenyl dicarboxylic acid, triphenyl dicarboxylic acid, 2,6-naphthalenedicarboxylic acid and their derivatives, or compounds obtained by substituting at least a portion of the hydrogen atoms of these aromatic rings with alkyl or halogen atoms. Examples of tetracarboxylic dianhydrides having the structure shown in formula (6) and / or formula (7) include acid dianhydrides having the structures shown below.

[0083] [Chemistry 12]

[0084] The total content of the structural units of polyimide, polyamide, polybenzoxazole, and their precursors having the structure shown in Formula (6) and / or Formula (7) is preferably 10 mol% or more and 80 mol% or less, more preferably 10 mol% or more and 65 mol% or less, and most preferably 10 mol% or more and 50 mol% or less in 100 mol% of the structural units of the total (A) resin.

[0085] Furthermore, to improve the storage stability of the resin composition, resin (A) is preferably end-capped with end-capping agents such as monoamines, acid anhydrides, monocarboxylic acids, monoacyl chloride compounds, and monoactive ester compounds. Moreover, by end-capping the ends of resin (A) with end-capping agents having hydroxyl, carboxyl, sulfonic acid, thiol, vinyl, ethynyl, or allyl groups, the dissolution rate of the resin in alkaline solutions and the mechanical properties of the resulting cured film can be easily adjusted to a preferred range. The proportion of the end-capping agent relative to 100 moles of the total amine content is preferably 0.1 moles or more, particularly preferably 5 moles or more, to suppress the increase in molecular weight of resin (A) and the decrease in solubility in alkaline solutions. Furthermore, to suppress the decrease in molecular weight of resin (A) and the resulting decrease in the mechanical properties of the cured film, the proportion of the end-capping agent is preferably 60 moles or less, particularly preferably 50 moles or less. By reacting various end-capping agents, a variety of different end groups can be introduced.

[0086] The compounds described in Japanese Patent Nos. 6740903

[0038] to

[0042] can be used as monoamines, acid anhydrides, monocarboxylic acids, monoacyl chloride compounds, or monoactive ester compounds.

[0087] Furthermore, in this invention, the capping agent introduced into the resin (A) can be easily detected by gas chromatography (GC), thermal decomposition gas chromatography (PGC), infrared spectroscopy and / or NMR.

[0088] (A) The resin preferably has a weight-average molecular weight of 10,000 or more and 100,000 or less. A weight-average molecular weight of 10,000 or more improves the mechanical properties of the cured film. A weight-average molecular weight of 20,000 or more is more preferred. On the other hand, a weight-average molecular weight of 100,000 or less improves the developability with various developing solutions, and a weight-average molecular weight of 50,000 or less improves the developability with alkaline solutions, which is also preferred.

[0089] The weight-average molecular weight (Mw) can be confirmed using GPC (gel permeation chromatography). For example, by using N-methyl-2-pyrrolidone (hereinafter sometimes simply referred to as NMP) as the eluent, the weight-average molecular weight can be calculated using polystyrene. Furthermore, if (A) resin contains two or more resins, it is sufficient that the weight-average molecular weight of at least one of them is within the above-mentioned range.

[0090] (A) The resin can be produced by known methods. (A) When the resin is a polyimide precursor, such as polyamic acid, polyamic ester, etc., as a first method, a method of reacting a tetracarboxylic dianhydride with a diamine compound at low temperature can be cited. Furthermore, as a second method, a method of obtaining a diester by reacting a tetracarboxylic dianhydride with an alcohol, followed by reaction with an amine and a condensing agent, can be cited. As a third method, a method of obtaining a diester by reacting a tetracarboxylic dianhydride with an alcohol, followed by acyl chloride of the remaining dicarboxylic acid, and synthesis by reaction with an amine, etc., can be cited.

[0091] (A) When the resin is a polybenzoxazole precursor, such as a polyhydroxyamide, a manufacturing method can be given as a method of condensing a diaminophenol compound with a dicarboxylic acid. Specifically, methods can be given as follows: reacting a dehydrating condensing agent such as dicyclohexylcarbodiimide (DCC) with an acid and adding the diaminophenol compound thereto; or adding a solution of dicarboxylic acid diacyl chloride dropwise to a solution of a diaminophenol compound containing a tertiary amine such as pyridine.

[0092] (A) When the resin is polyimide, it can be obtained, for example, by dehydrating and cyclizing the polyimide precursor obtained by the aforementioned method through heat treatment or chemical treatment such as acid or alkali. When it is polybenzoxazole, it can be obtained, for example, by dehydrating and cyclizing the polybenzoxazole precursor obtained by the aforementioned method through heat treatment or chemical treatment such as acid or alkali.

[0093] <(B-1) Compounds that produce acids through light> The resin composition of the present invention preferably contains (B-1) a compound that generates acid upon exposure to light. By containing the (B-1) component, the resin composition can be imparted with photosensitivity.

[0094] (B-1) A compound that generates acid through light produces acid at the light-irradiated portion of the resin composition. As a result, the solubility of the light-irradiated portion in the alkaline developer increases, thus enabling the acquisition of a positive pattern that dissolves in the light-irradiated portion.

[0095] Examples of compounds that generate acids via light, as described in (B-1), include diazonium compounds, sulfonium salts, phosphonium salts, diazonium salts, and iodonium salts. The resin composition of the present invention may further include sensitizers, etc., as needed.

[0096] As a diazonoquinone compound, it is preferred to be a compound obtained by ester bonding a sulfonic acid of diazonoquinone to a compound having a phenolic hydroxyl group.

[0097] Examples of compounds containing phenolic hydroxyl groups include Bis-Z, BisP-EZ, TekP-4HBPA, TrisP-HAP, TrisP-PA, TrisP-SA, TrisOCR-PA, BisOCHP-Z, BisP-MZ, BisP-PZ, BisP-IPZ, BisOCP-IPZ, BisP-CP, BisRS-2P, BisRS-3P, BisP-OCHP, methylenetri-FR-CR, BisRS-26X, DML-MBPC, DMLMBOC, DML-OCHP, DML-PCHP, DML-PC, DML-PTBP, DML-34X, DML-EP, DML-POP, dihydroxymethyl-BisOC-P, DML-PFP, DML-PSBP, DML-MTrisPC, TriML-P, and Tri... Compounds including ML-35XL, TML-BP, TML-HQ, TML-ppBPF, TML-BPA, TMOM-BP, HML-TPPHBA, HML-TPHAP (trade name, manufactured by Honshu Chemical Industry Co., Ltd.), BIR-OC, BIP-PC, BIR-PC, BIR-PTBP, BIR-PCHP, BIP-BIOC-F, 4PC, BIR-BIPC-F, TEP-BIP-A, 46DMOC, 46DMOEP, TM-BIP-A (trade name, manufactured by Asahi Organic Materials Co., Ltd.), 2,6-dimethoxymethyl-4-tert-butylphenol, 2,6-dimethoxymethyl-p-cresol, 2,6-diacetoxymethyl-p-cresol, naphthol, tetrahydroxybenzophenone, methyl gallate, bisphenol A, bisphenol E, methylene bisphenol, BisP-AP (trade name, manufactured by Honshu Chemical Industry Co., Ltd.), etc.

[0098] Examples of sulfonic acids that are diazononaphthoquinones include 4-diazonaphthoquinone sulfonic acid and 5-diazonaphthoquinone sulfonic acid.

[0099] Furthermore, at least 50 mol% of the functional groups of the compound having phenolic hydroxyl groups are preferably replaced by diazonoquinone. By using at least 50 mol% of the substituted diazonoquinone compound, the affinity of the diazonoquinone compound for alkaline aqueous solutions is reduced. As a result, the solubility of the resin composition in the unexposed portion of the composition in alkaline aqueous solutions is significantly reduced. Furthermore, through exposure, the diazonoquinone sulfonyl group is converted to indica acid, resulting in a high solubility rate of the photosensitive resin composition in the exposed portion of the composition in alkaline aqueous solutions. That is, as a result, the solubility rate ratio of the exposed portion to the unexposed portion of the composition is increased, enabling the acquisition of patterns at high resolution.

[0100] By containing such a diazonoquinone compound, a photosensitive resin composition with positive photosensitive properties can be obtained, which is sensitive to the i-line (365 nm), h-line (405 nm), g-line (436 nm), and the broadband containing them of a common mercury lamp. Furthermore, component (B-1) can be contained in only one form or in combination of two or more forms, resulting in a photosensitive resin composition with high sensitivity.

[0101] As a diazonoquinone, either 5-diazonaphthoquinone sulfonyl or 4-diazonaphthoquinone sulfonyl is preferred. The 5-diazonaphthoquinone sulfonyl ester compound has absorption extending into the g-line region of the mercury lamp, making it suitable for both g-line and full-wavelength exposure. The 4-diazonaphthoquinone sulfonyl ester compound has absorption in the i-line region of the mercury lamp, making it suitable for i-line exposure. Depending on the exposure wavelength, either the 4-diazonaphthoquinone sulfonyl ester compound or the 5-diazonaphthoquinone sulfonyl ester compound is preferred.

[0102] Furthermore, diazonaquinone sulfonyl ester compounds containing both 4-diazonaphthoquinone sulfonyl and 5-diazonaphthoquinone sulfonyl groups in the same molecule can also be obtained. Combinations of 4-diazonaphthoquinone sulfonyl ester compounds and 5-diazonaphthoquinone sulfonyl ester compounds can also be used. Diazoquinone compounds can be synthesized by known methods through the esterification reaction of compounds with phenolic hydroxyl groups and diazonone sulfonic acid compounds. Using diazonquinone compounds further improves resolution, sensitivity, and film retention.

[0103] The molecular weight of component (B-1) is preferably 300 or more, more preferably 350 or more, more preferably 3,000 or less, and more preferably 1,500 or less, from the viewpoint of the heat resistance, mechanical properties and adhesion of the film obtained by heat treatment.

[0104] Of the components in (B-1), sulfonium salt, phosphonium salt, and diazonium salt are preferred as they moderately stabilize the acid components generated by exposure. Among these, sulfonium salt is preferred.

[0105] The content of component (B-1) is preferably 0.1 parts by mass or more and 100 parts by mass or less relative to 100 parts by mass of resin (A). If the content of component (B-1) is 0.1 parts by mass or more and 100 parts by mass or less, photosensitivity can be imparted while maintaining the heat resistance, chemical resistance and mechanical properties of the film after heat treatment.

[0106] When component (B-1) contains a diazonium quinone compound, the content of component (B-1) relative to 100 parts by weight of resin (A) is more preferably 1 part by weight or more, and even more preferably 3 parts by weight or more. Furthermore, it is more preferably 100 parts by weight or less, and even more preferably 80 parts by weight or less. If it is 1 part by weight or more and 100 parts by weight or less, photosensitivity can be imparted while maintaining the heat resistance, chemical resistance, and mechanical properties of the film after heat treatment.

[0107] When component (B-1) contains sulfonium salt, phosphonium salt, or diazonium salt, the content of component (B-1) relative to 100 parts by weight of resin (A) is more preferably 0.1 parts by weight or more, further preferably 1 part by weight or more, and particularly preferably 3 parts by weight or more. Furthermore, it is more preferably 100 parts by weight or less, further preferably 80 parts by weight or less, and particularly preferably 50 parts by weight or less. If it is 0.1 parts by weight or more and 100 parts by weight or less, photosensitivity can be imparted while maintaining the heat resistance, chemical resistance, and mechanical properties of the film after heat treatment.

[0108] <(C-1) Thermal crosslinking agent> The resin composition of the present invention preferably contains a (C-1) thermal crosslinking agent. In the present invention, a thermal crosslinking agent refers to a compound containing at least two groups selected from acryloyl, methacryl, epoxy, oxetyl, benzoxazine, alkoxymethyl, and hydroxymethyl groups. The content of the (C-1) component is preferably 10 parts by mass or less relative to 100 parts by mass of resin (A). By setting it within this range, a wide range of designs for improving sensitivity and the mechanical properties of the cured film can be easily and appropriately implemented.

[0109] (C-1) The thermal crosslinking agent preferably comprises a compound having at least two alkoxymethyl or hydroxymethyl groups. Here, "having at least two alkoxymethyl or hydroxymethyl groups" means having two or more alkoxymethyl groups, having two or more hydroxymethyl groups, or having a total of two or more alkoxymethyl and hydroxymethyl groups. By having at least two of these groups, a crosslinked structure can be formed by condensation reaction with the resin and the same molecule. By including a compound having at least two alkoxymethyl or hydroxymethyl groups together with component (B-1), a wide range of designs for improving sensitivity and the mechanical properties of the cured film can be implemented.

[0110] Preferred examples of compounds having at least two alkoxymethyl or hydroxymethyl groups include, for example, DML-PC, DML-PEP, DML-OC, DML-OEP, DML-34X, DML-PTBP, DML-PCHP, DML-OCHP, DML-PFP, DML-PSBP, DML-POP, DML-MBOC, DML-MBPC, DML-MTrisPC, DML-BisOC-Z, DMLBisOCHP-Z, DML-BPC, DML-BisOC-P, DMOM-PC, DMOM-PTBP, and DMOM. -MBPC, TriML-P, TriML-35XL, TML-HQ, TML-BP, TML-pp-BPF, TML-BPE, TML-BPA, TML-BPAF, TML-BPAP, TMOM-BP, TMOM-BPE, TMOM-BPA, TMOM-BPAF, TMOM-BPAP, HML-TPPHBA, HML-TPHAP, HMOM-TPPHBA, HMOM-TPHAP (the above are trade names, manufactured by Honshu Chemical Industry Co., Ltd.), NIKALAC (registered trademark) MX-290, NIKALAC MX-280, NIKALAC MX-270, NIKALAC MX-279, NIKALAC MW-100LM, NIKALAC MX-750LM (the above are trade names, manufactured by Sanwa Kemikal Co., Ltd.). These may contain two or more types. Among them, the presence of HMOM-TPHAP and MW-100LM makes it difficult to cause reflow during curing, resulting in a high rectangular pattern, which is therefore preferred.

[0111] The content of compounds having at least two alkoxymethyl or hydroxymethyl groups is preferably set to 10 parts by weight or less per 100 parts by weight of resin (A). If it is within this range, a wider range of designs for improving sensitivity and the mechanical properties of the cured film can be more appropriately made.

[0112] <(B-2) Photopolymerization Initiator> The resin composition of the present invention preferably contains a (B-2) photopolymerization initiator. By containing the (B-2) component, the resin composition can be imparted with photosensitivity. The (B-2) photopolymerization initiator is not particularly limited to any compound that generates free radicals through exposure; alkyl phenyl ketone compounds, aminobenzophenone compounds, diketone compounds, ketone ester compounds, phosphine oxide compounds, oxime ester compounds, and benzoate ester compounds are preferred due to their excellent sensitivity, stability, and ease of synthesis. From the viewpoint of sensitivity, alkyl phenyl ketone compounds and oxime ester compounds are preferred, and oxime ester compounds are particularly preferred. Furthermore, when processing a thick film with a thickness of 5 μm or more, from the viewpoint of resolution, a phosphine oxide compound is preferred.

[0113] Examples of alkylphenyl ketone compounds include α-aminoalkylphenyl ketone compounds, α-hydroxyalkylphenyl ketone compounds, and α-alkoxyalkylphenyl ketone compounds. From the viewpoint of high sensitivity, α-aminoalkylphenyl ketone compounds are preferred. Examples of α-aminoalkylphenyl ketone compounds include 2-methyl-[4-(methylthio)phenyl]-2-morpholinopropane-1-one and 2-dimethylamino-2-(4-methylbenzyl)-1-(4-morpholino-4-yl-phenyl)-butane-1-one. Examples of α-hydroxyalkylphenyl ketone compounds include 1-hydroxycyclohexylphenyl ketone and benzoin. Examples of α-alkoxyalkylphenyl ketone compounds include 4-benzoyl-4-methylphenyl ketone and 2,3-diethoxyacetophenone.

[0114] Examples of phosphine oxide compounds include, for instance, 6-trimethylbenzoylphenylphosphine oxide.

[0115] Examples of oxime ester compounds include 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]-, 1-(0-acetyl oxime), 2-octanedione, 1-[4-(phenylthio)-2-(O-benzoyl oxime)], NCI-831, NCI-930 (trade names, manufactured by ADEKA Co., Ltd.), "Irgacure (registered trademark)" OXE-03, OXE-04 (trade names, manufactured by BASF Co., Ltd.).

[0116] Examples of aminobenzophenone compounds include 4,4-bis(dimethylamino)benzophenone. Examples of diketone compounds include benzoyl. Examples of ketone ester compounds include methyl benzoylformate. Examples of benzoic acid ester compounds include methyl o-benzoylbenzoate and ethyl p-dimethylaminobenzoate.

[0117] Other specific examples of (B-2) photopolymerization initiators include benzophenone, 4-benzoyl-4′-methyldiphenyl ketone, benzomethyl ketone, fluorenone, thioxanthone, 2-methylthioxanthone, 2-isopropylthioxanthone, 2-hydroxy-3-(3,4-dimethyl-9-oxo-9H-thioxanth-2-yloxy)-N,N,N-trimethyl-1-propanenium chloride, anthraquinone, triphenylphosphine, carbon tetrabromide, etc.

[0118] When the sum of the contents of resin (A) and compounds having two or more olefinic unsaturated bonds, as needed, is 100 parts by mass, it is preferable that the content of photopolymerization initiator (B-2) is 0.5 parts by mass or more and 20 parts by mass or less to obtain sufficient sensitivity and suppress degassing during thermosetting. More preferably, it is 1.0 parts by mass or more and 10 parts by mass or less.

[0119] The resin composition of the present invention may contain a sensitizer. By containing a sensitizer, the function of the (B-2) photopolymerization initiator can be further improved, thereby increasing sensitivity and adjusting the photosensitivity wavelength. Examples of sensitizers include, but are not limited to, bis(dimethylamino)benzophenone, bis(diethylamino)benzophenone, diethylthioxanthone, N-phenyldiethanolamine, N-phenylglycine, 7-diethylamino-3-benzoylcoumarin, 7-diethylamino-4-methylcoumarin, N-phenylmorpholine, and their derivatives.

[0120] <(C-2) Compounds with two or more olefinic unsaturated bonds> The resin composition of the present invention preferably further contains a compound (C-2) having two or more olefinic unsaturated bonds. By containing the (C-2) component, photosensitivity can be imparted. Furthermore, the crosslinking density during exposure is increased, thus further improving exposure sensitivity and contributing to a reduction in exposure amount and thinning of the developing film. As the (C-2) component, a polyfunctional (meth)acrylate compound may be contained.

[0121] Examples of multifunctional (meth)acrylate compounds include diethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, 1,3-butanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, pentaerythritol tetra(meth)acrylate, ethoxylated bisphenol A di(meth)acrylate, and 9,9-bis[4-(2- [(meth)acryloyloxyethoxy)phenyl]fluorene, dihydroxymethyl-tricyclodecane di(meth)acrylate, 1,3-adamantanediol di(meth)acrylate, 1,3,5-adamantanetriol di(meth)acrylate, 1,3,5-adamantanetriol tri(meth)acrylate, 1,4-cyclohexanediethanol di(meth)acrylate, 5-hydroxy-1,3-adamantane di(meth)acrylate, EO-modified hydrogenated bisphenol A di(meth)acrylate, etc.

[0122] Other examples of polyfunctional (meth)acrylate compounds include epoxy (meth)acrylates obtained by reacting polyfunctional epoxy compounds with (meth)acrylic acid.

[0123] The content of component (C-2) relative to 100 parts by weight of resin (A) is preferably 5 parts by weight or more and 100 parts by weight or less, more preferably 10 parts by weight or more and 40 parts by weight or less. By setting the content of component (C-2) within the aforementioned range, mechanical properties can be easily maintained while improving sensitivity.

[0124] <Compounds shown in formula (5) (D)> The resin composition of the present invention preferably further contains the compound represented by formula (D) (5) (hereinafter sometimes simply referred to as component (D)).

[0125] [Chemistry 13]

[0126] In equation (5), R 9 R represents an alkyl group with 1 or more but less than 15 carbon atoms. 10 R indicates an alkylene group with 2 or more but less than 10 carbon atoms. 11 This refers to an alkyl group with 1 or more but less than 20 carbon atoms, an alkylene group with 1 or more but less than 20 carbon atoms, or a monovalent to tetravalent organic group containing at least one of O, S, and N atoms, with 1 to 20 carbon atoms. k represents an integer from 1 to 4. As R 11Examples of substituents include quaternary carbonyl, tertiary carbonyl, secondary carbonyl, alkyl, cycloalkyl, alkoxy, alkyl ether, alkylsilyl, alkoxysilyl, aryl, aryl ether, carboxyl, carbonyl, allyl, vinyl, heterocyclic, -O-, -NH-, -NHNH-, and combinations thereof, and substituents may be present. From the viewpoint of solubility in the developer and metal adhesion, alkyl ether or -NH- is preferred, and from the viewpoint of interaction with resin (A) and metal adhesion achieved through metal complexation, -NH- is more preferred.

[0127] By including component (D), the oxidative degradation of the aliphatic groups and hydroxyl groups of resin (A) is easily suppressed. Furthermore, through its rust-preventive effect on metal materials, it easily suppresses metal oxidation caused by external moisture, photosensitizers, etc., and the associated peeling between the cured film and the metal material. In other words, it can easily suppress the degradation of device characteristics after reliability testing. Specific examples of component (D) include the following substances, but are not limited to them; other compounds may also be used.

[0128] [Chemistry 14]

[0129] [Chemistry 15]

[0130] Furthermore, the amount of component (D) added relative to 100 parts by weight of resin (A) is preferably 0.1 to 10 parts by weight, more preferably 0.2 to 5 parts by weight. Adding 0.1 parts by weight or more improves adhesion to metal materials while suppressing peeling. Adding 10 parts by weight or less maintains the sensitivity of the resin composition.

[0131] <Sealing Modifier> The resin composition of the present invention may contain a binding modifier. Examples of binding modifiers include vinyltrimethoxysilane, vinyltriethoxysilane, epoxycyclohexylethyltrimethoxysilane, 3-epoxypropoxypropyltrimethoxysilane, 3-epoxypropoxypropyltriethoxysilane, p-styryltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, and other silane coupling agents, titanium chelating agents, aluminum chelating agents, and compounds obtained by reacting aromatic amine compounds with alkoxy-containing silicon compounds. Two or more of these modifiers may be present.

[0132] By including an adhesion modifier, the adhesion to substrates such as silicon wafers, ITO, SiO2, and silicon nitride can be improved during resin film development. Furthermore, resistance to oxygen plasma and UV ozone treatments used in washing processes can be enhanced.

[0133] The content of the adhesion modifier in the resin composition is preferably 0.1 to 10 parts by weight relative to 100 parts by weight of resin (A). By setting it within this range, a resin composition with high adhesion after development and excellent resistance to oxygen plasma and UV ozone treatment can be provided.

[0134] <Compounds with phenolic hydroxyl groups> The resin composition of the present invention, from the viewpoint of easily compensating for alkaline developability, may contain compounds having phenolic hydroxyl groups. The resin composition containing compounds having phenolic hydroxyl groups is almost insoluble in alkaline developing solution before exposure, but readily dissolves in alkaline developing solution upon exposure. Therefore, film thinning due to development is minimal, and development is easily achieved in a short time. Consequently, sensitivity is easily improved.

[0135] Examples of compounds with phenolic hydroxyl groups selected from the aforementioned viewpoint include, for instance, Bis-Z, BisOC-Z, BisOPP-Z, BisP-CP, Bis26X-Z, BisOTBP-Z, BisOCHP-Z, BisOCR-CP, BisP-MZ, BisP-EZ, Bis26X-CP, BisP-PZ, BisP-IPZ, BisCRIPZ, BisOCP-IPZ, BisOIPP-CP, Bis26X-IPZ, BisOTBP-CP, TekP-4HBPA (tetra-P-DO-BPA), TrisPHAP, TrisPPA, TrisP-PHBA, TrisP-SA, TrisOCR-PA, BisOFP-Z, BisRS-2P, BisPG-26X, BisRS-3P, BisOC-OCHP, and BisPC. -OCHP, Bis25X-OCHP, Bis26X-OCHP, BisOCHP-OC, Bis236T-OCHP, Methylene Tri-FR-CR, BisRS-26X, BisRS-OCHP (trade name, manufactured by Honshu Chemical Industry Co., Ltd.), BIR-OC, BIP-PC, BIR-PC, BIR-PTBP, BIR-PCHP, BIP-BIOC-F, 4PC, BI R-BIPC-F, TEP-BIP-A (trade name, manufactured by Asahi Organic Materials Co., Ltd.), 1,4-dihydroxynaphthalene, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 1,7-dihydroxynaphthalene, 2,3-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, 2,7-dihydroxynaphthalene, 2,4-dihydroxyquinoline, 2,6-dihydroxyquinoline, 2,3-dihydroxyquinoxaline, anthracene-1,2,10-triol, anthracene-1,8,9-triol, 8-quinolinol, etc. They may contain two or more of these compounds.

[0136] Furthermore, from the viewpoint of shortening the development time, the resin composition of the present invention can contain a compound having phenolic hydroxyl groups within a range that does not reduce the shrinkage rate of the cured film.

[0137] Examples of compounds containing phenolic hydroxyl groups selected from the aforementioned viewpoint include Bis-Z, BisP-EZ, TekP-4HBPA, TrisP-HAP, TrisP-PA, BisOCHP-Z, BisP-MZ, BisP-PZ, BisP-IPZ, BisOCP-IPZ, BisP-CP, BisRS-2P, BisRS-3P, BisP-OCHP, methylene tri-FR-CR, BisRS-26X (trade names, manufactured by Honshu Chemical Industry Co., Ltd.), BIP-PC, BIR-PC, BIR-PTBP, and BIR-BIPC-F (trade names, manufactured by Asahi Organic Materials Co., Ltd.). These compounds may contain two or more of these hydroxyl groups.

[0138] <surfactants> The resin composition of the present invention may contain a surfactant as needed. By containing a surfactant, the wettability with the substrate can be improved, or the film thickness uniformity of the coated film can be improved. Commercially available compounds can be used as surfactants. Specifically, examples of silicone-based surfactants include the SH, SD, and ST series from Toredo Konigen Gesilicon Co., Ltd., the BYK series from Vitzkukemi-Jayapan Co., Ltd., the KP series from Shin-Etsu Silicon Co., Ltd., the Daysfield series from Nippon Yushi Co., Ltd., and the TSF series from Toshiba Silicon Co., Ltd. Examples of fluorinated surfactants include Dai Nippon Inki Kogyo Co., Ltd.'s "Mega-Aatsuku" (registered trademark) series, Sumitomo Sli-Em Co., Ltd.'s Florad series, Asahi Glass Co., Ltd.'s "Sa-Fron" (registered trademark) series, "Asahigard" (registered trademark) series, Shin-Akita Kasei Co., Ltd.'s EF series, and Saimunovia Induction Co., Ltd.'s Polyfrotsukus series. Examples of surfactants derived from acrylic and / or methacrylic polymers include Kyoeisha Chemical Co., Ltd.'s Polyfrot series and Kusumoto Kasei Co., Ltd.'s "Dyes Paraf" (registered trademark) series, but these are not limited to these examples.

[0139] The surfactant content is preferably 0.001 parts by mass or more and 1 part by mass or less per 100 parts by mass of resin (A). By setting it within the above range, defects such as bubbles and pinholes are not generated, and the wettability of the resin composition to the substrate and the uniformity of the coating film thickness can be improved.

[0140] <(E)solvent> The resin composition of the present invention contains (E) solvent (hereinafter sometimes referred to as (E) component). Examples of (E) solvents include polar aprotic solvents such as N-methyl-2-pyrrolidone, γ-butyrolactone, γ-valerolactone, δ-valerolactone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, 1,3-dimethyl-2-imidazolium ketone, N,N′-dimethylpropylene urea, N,N-dimethylisobutyramide, and methoxy-N,N-dimethylpropionamide; ethers such as tetrahydrofuran, dioxane, propylene glycol monomethyl ether, and propylene glycol monoethyl ether; ketones such as acetone, methyl ethyl ketone, and diisobutyl ketone; esters such as ethyl acetate, butyl acetate, isobutyl acetate, propyl acetate, propylene glycol monomethyl ether acetate, and 3-methyl-3-methoxybutyl acetate; alcohols such as ethyl lactate, methyl lactate, diacetone alcohol, and 3-methyl-3-methoxybutanol; and aromatic hydrocarbons such as toluene and xylene. They can contain more than two types.

[0141] The content of solvent (E) relative to 100 parts by weight of resin (A) is preferably 100 parts by weight or more from the viewpoint of easily dissolving the composition. Furthermore, the content of solvent (E) is preferably 1,500 parts by weight or less from the viewpoint of easily forming a coating film with a thickness of 1 μm or more.

[0142] <Method for manufacturing resin compositions> Next, a method for manufacturing the resin composition of the present invention will be described. For example, a resin composition can be obtained by mixing and dissolving the aforementioned components (A) and (E) with, as needed, components (B), (C), (D), a binding modifier, a surfactant, etc. It should be noted that in the present invention, component (B) is a collective term for components (B-1) and (B-2). Furthermore, component (C) is a collective term for components (C-1) and (C-2).

[0143] Examples of dissolution methods include heating and stirring. When heating, the heating temperature is preferably set within a range that does not impair the properties of the resin composition, typically between 25°C and 80°C. Furthermore, the order in which the components are dissolved is not particularly limited; for example, methods can be used to dissolve compounds with low solubility sequentially. When stirring, the rotation speed is preferably set within a range that does not impair the properties of the resin composition, typically between 200 rpm and 2000 rpm. Heating may also be performed while stirring, typically between 25°C and 80°C. Moreover, for components such as surfactants and partial binders that are prone to generating bubbles during stirring, adding them last after dissolving other components can prevent poor dissolution of other components due to bubble formation.

[0144] The viscosity of the resin composition of the present invention is preferably 2 to 5,000 mPa·s at 25°C. The desired film thickness can be easily obtained by adjusting the solid component concentration to achieve a viscosity of 2 mPa·s or higher. On the other hand, if the viscosity is 5,000 mPa·s or lower, a coating film with high uniformity is easily obtained. The viscosity was measured using a TVE-25 type viscometer (manufactured by Toki Sangyo Co., Ltd.), specifically an older E-type or DVE-type viscometer. 1.1 mL of the resin composition of the present invention was collected and injected into a sample cup. Depending on the viscosity, the torque was selected within the range of 65 to 6000 μN·m, and the rotational speed was measured within the range of 0.5 to 100 rpm. The resin composition of the present invention having such viscosity can be easily obtained by setting the total content of component (A) in 100% by mass of the resin composition of the present invention, and, if present, components (B) and (C), to 5 to 60% by mass. Here, the solid component concentration refers to the components other than the solvent.

[0145] The resulting resin composition is preferably filtered using a filter to remove impurities and particles. Filter pore sizes include, for example, 0.5 μm, 0.2 μm, 0.1 μm, 0.05 μm, and 0.02 μm, but are not limited to these. Filter materials include polypropylene (PP), polyethylene (PE), nylon (NY), and polytetrafluoroethylene (PTFE), with polyethylene and nylon being preferred.

[0146] <Cured film> The cured film of the present invention is obtained by curing the resin composition of the present invention in a first manner. The cured film exhibits excellent heat resistance, mechanical properties, and chemical resistance.

[0147] Furthermore, a second aspect of the cured film of the present invention is a cured film having a resin (A), wherein the resin (A) comprises at least one selected from polyimide, polyamide, polybenzoxazole, their precursors and their copolymers, and the resin (A) has the structure shown in formula (1).

[0148] [Chemistry 16]

[0149] In equation (1), a is an independent integer from 0 to 4, b is an independent integer from 0 to 2, and when b is 0, the part in parentheses represents a single bond, and n is an integer from 1 to 12. A is an independent single bond, -O-, -S-, -CO-, -COO-, -OCO-, -NHCO-, -CONH-, or a divalent hydrocarbon group with 1 to 5 carbon atoms, R 1 Each of these can be independently represented by a halogen atom, a hydroxyl group, a monovalent hydrocarbon group with 1 to 6 carbon atoms, an alkoxy group with 1 to 6 carbon atoms, or a phenoxy group. * indicates a chemical bond. The structure of component (A) and formula (1) is the same as that described in the above-described composition.

[0150] The cured film of the present invention did not show a decrease in elongation after the encapsulation reliability test, and has high crack resistance, which can improve the reliability of the semiconductor device, electronic component and display device of the present invention.

[0151] The cured film of the present invention can be manufactured, for example, by the following methods.

[0152] First, the resin composition of the present invention is coated onto a substrate and dried to obtain a resin film. Next, the resin film is heat-treated to obtain the cured film of the present invention.

[0153] The heat treatment of the resin film can be carried out in stages or simultaneously with continuous heating. The heat treatment is preferably performed for 5 minutes to 5 hours. For example, a further heat treatment at 320°C for 60 minutes after heat treatment at 140°C for 30 minutes is recommended. The heat treatment temperature is preferably 140°C or higher and 400°C or lower. To remove solvent from the resin film, the heat treatment temperature is preferably 140°C or higher, more preferably 160°C or higher. Furthermore, to provide an excellent cured film and improve yield, the heat treatment temperature is preferably 400°C or lower, more preferably 350°C or lower.

[0154] <Insulating film, protective film> The insulating film or protective film of the present invention has the cured film of the present invention. Specific examples of the insulating film or protective film include passivation films for semiconductors, surface protective films for semiconductor devices, interlayer insulating films, interlayer insulating films for multilayer wiring for high-density mounting, insulating layers for organic electroluminescent devices, etc., but are not limited thereto, and various structures can be cited.

[0155] The insulating or protective film of the present invention has high mechanical properties during curing and maintains the same mechanical properties after reliability testing as before reliability testing, thus enabling the provision of a highly reliable semiconductor device exhibiting high crack resistance.

[0156] <Electronic components, display devices or semiconductor devices, and methods of manufacturing them> The method for manufacturing an electronic component, display device, or semiconductor device of the present invention includes the steps of: coating a resin composition of the present invention and drying it to form a resin film; irradiating the resin film with chemical rays; developing the resin film to form a pattern; and performing heat treatment to form a textured pattern layer of a cured film.

[0157] In the step of coating and drying the resin composition of the present invention to form a resin film, the resin composition of the present invention is first coated onto a substrate to obtain a coated film of the resin composition. Examples of substrates include, but are not limited to, silicon wafers, ceramics, gallium arsenide, organic circuit boards, inorganic circuit boards, and substrates obtained by disposing of circuits on these substrates.

[0158] Examples of coating methods include spin coating, slot coating, dip coating, spray coating, and printing. Furthermore, the coating thickness varies depending on the coating method, the concentration of solid components in the composition, and the viscosity, and is typically achieved by coating to a thickness of 0.1–150 μm after drying.

[0159] Before coating, the substrate to which the resin composition is to be coated can be pretreated with the aforementioned adhesion modifier. Examples of pretreatment methods include using a solution obtained by dissolving the adhesion modifier in solvents such as isopropanol, ethanol, methanol, water, tetrahydrofuran, propylene glycol monomethyl ether acetate, propylene glycol monomethyl ether, ethyl lactate, and diethyl adipate at 0.5–20% by mass, and then treating the substrate surface by spin coating, slot die coating, rod coating, dip coating, spray coating, or steam treatment. After treating the substrate surface, a vacuum drying process can be performed as needed. Furthermore, a subsequent heat treatment at 50°C to 280°C can induce a reaction between the substrate and the adhesion modifier.

[0160] Next, the coating film of the resin composition is dried to form a resin film. Drying is preferably carried out using an oven, heating plate, infrared radiation, etc., at a temperature of 50°C to 140°C for 1 minute to 2 hours.

[0161] In the step of irradiating the resin film with chemical rays, the photosensitive resin film is exposed by irradiating it with chemical rays through a mask having a desired pattern. Chemical rays used for exposure include ultraviolet light, visible light, electron beams, X-rays, etc. In this invention, chemical rays containing common exposure wavelengths, namely g-rays (436 nm), h-rays (405 nm), or i-rays (365 nm), are preferred.

[0162] The manufacturing method of the electronic component, display device, or semiconductor device of the present invention may, as needed, include a post-exposure baking (PEB) step. Preferably, the PEB step involves baking the exposed resin film at a temperature of 50°C to 150°C for 1 minute to 2 hours using an oven, heating plate, infrared radiation, or similar means.

[0163] As the developing solution used in the step of developing a resin film to form a pattern, if the resin composition is alkali-soluble, an aqueous solution of a compound exhibiting alkalinity, such as tetramethylammonium, diethanolamine, diethylaminoethanol, sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, triethylamine, diethylamine, methylamine, dimethylamine, dimethylaminoethyl acetate, dimethylaminoethanol, dimethylaminoethyl methacrylate, cyclohexylamine, ethylenediamine, or hexamethylenediamine, may be added, depending on the circumstances. Furthermore, one or more of the following may be added to the aqueous solution of these alkaline compounds: polar solvents such as N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, γ-butyrolactone, or dimethylacrylamide; alcohols such as methanol, ethanol, or isopropanol; esters such as ethyl lactate or propylene glycol monomethyl ether acetate; and ketones such as cyclopentanone, cyclohexanone, isobutyl ketone, or methyl isobutyl ketone. When the resin composition is not alkali-soluble, the developer is preferably a good solvent for the resin composition, or a combination of a good solvent and a poor solvent. Examples of good solvents include N-methylpyrrolidone, N,N-dimethylacetamide, cyclopentanone, cyclohexanone, and γ-butyrolactone. Examples of poor solvents include toluene, xylene, ethanol, isopropanol, ethyl lactate, propylene glycol monomethyl ether acetate, and water. When a good solvent and a poor solvent are used in combination, the ratio of the poor solvent to the good solvent is preferably adjusted according to the solubility of the polymer in the resin composition. Furthermore, two or more solvents, for example, multiple solvents, can be used in combination. After development, rinsing is generally performed with an organic solvent or water. Here, rinsing can also be performed by adding alcohols such as ethanol and isopropanol, esters such as ethyl lactate and propylene glycol monomethyl ether acetate.

[0164] Dry etching can be used as a method for patterning the resin composition. Specifically, it includes the steps of coating the resin composition of the present invention onto a substrate; evaporating the solvent (E) at a temperature of 80°C or higher and below 150°C; curing at a temperature of 150°C or higher and below 350°C; and abrasion processing by a carbonic acid laser or a UV laser. The irradiation conditions for the UV laser are not particularly limited, and excimer lasers such as ArF (193nm), KrF (248nm), XeCl (308nm), and XeCl (351nm), as well as YAG lasers (355nm), are commonly used. While carbonic acid lasers have lower resolution than UV lasers, they are inexpensive. From an economic point of view, carbonic acid lasers can be used in applications where high precision is not required.

[0165] The method for manufacturing an electronic component, display device, or semiconductor device of the present invention includes the step of forming a textured pattern layer of a cured film by heat treatment. The preferred conditions for the heat treatment are the same as those for the resin film in the <cured film> section described above.

[0166] As an example of a method for manufacturing an electronic component, display device, or semiconductor device according to the present invention, a method for manufacturing a semiconductor device using a redistribution layer (RDL) priority step is shown. A barrier metal such as Ti is formed on a support substrate such as a glass substrate or silicon wafer by sputtering. A Cu seed crystal (seed layer) is then formed on the substrate by sputtering, followed by the formation of an electrode pad containing Cu by plating. Next, the resin composition of the present invention is coated onto the entire surface of the support substrate on which the electrode pad has been formed, and dried to form a resin film. The resulting resin film is irradiated with an i-line stepper, a broadband aligner, or the like at 100–2000 mJ / cm². 2 The exposed resin film is then exposed to chemical rays. Next, a developing solution is sprayed onto the exposed resin film, dissolving and removing the exposed portions, thus developing the film and forming a pattern of lines and spacings, squares, or holes. Then, heat treatment is performed to form a textured pattern layer of the cured film. This textured pattern layer forms an insulating film. Next, a seed layer is formed again by sputtering, and a metal wiring (rewiring) containing Cu is formed by plating. The seed layer step and the metal wiring formation step are repeated to form a multilayer wiring structure. Next, the resin composition of the present invention is coated again, and after pattern formation using a chemical irradiation step, it is heat-treated and cured to form an insulating film. Cu pillars are then formed on the metal wiring in the openings of the insulating film using plating. Here, the spacing of the Cu pillars is set to be equal to the spacing of the conductive portions of the semiconductor chip. That is, the spacing of the conductive portions of the semiconductor chip is a finer spacing than the spacing of the electrode pads, and the rewiring layers constituting the multilayer wiring structure gradually become finer from the electrode pads to the Cu pillars, thus multiplying the wiring. In a multilayer wiring structure, the thickness of adjacent insulating films is either the same or thinner relative to the semiconductor chip. Next, the semiconductor chip is connected to the Cu pillars via solder bumps. Thus, the electrode pads and the semiconductor chip are electrically connected via metal wiring and solder bumps. Subsequently, the semiconductor chip is sealed with sealing resin to form a semiconductor package. Then, the support substrate is peeled away from the redistribution layer to separate the semiconductor package. In this way, a semiconductor device with a multilayer wiring structure using RDL-first steps can be obtained.

[0167] The first embodiment of the electronic component, display device, or semiconductor device of the present invention includes a textured pattern layer of the cured film of the present invention. By having a textured pattern layer of the cured film of the present invention, a highly reliable electronic component, display device, or semiconductor device can be obtained where no cracks are generated in the textured pattern layer after a packaging reliability test. Examples of the first embodiment of the electronic component, display device, or semiconductor device of the present invention include, for example, the electronic component, display device, or semiconductor device described in Japanese Patent Application Publication No. 2020-66651.

[0168] A second embodiment of the electronic component, display device, or semiconductor device of the present invention involves configuring the cured film of the present invention as an insulating film between wirings. By configuring the cured film of the present invention as an insulating film between wirings, a multilayer wiring structure in which two or more rewiring layers are separated by an insulating film containing a cured resin composition of the present invention can be formed. Generally, in packages with multilayer wiring structures, applying strong stress to the insulating film can lead to cracking after package reliability testing. By using an insulating film containing a cured resin composition of the present invention, a highly reliable package that does not crack after package reliability testing can be obtained. There is no upper limit to the number of layers in a multilayer wiring structure; most commonly, 10 layers or less are used.

[0169] In the second aspect of the electronic component, display device, or semiconductor device of the present invention, examples of semiconductor devices include, for instance, chip-first fan-out wafer-level packaging or chip-first fan-out panel-level packaging. Chip-first fan-out wafer-level packaging or chip-first fan-out panel-level packaging refers to a semiconductor package in which an expansion portion is provided around the semiconductor chip using a sealing resin such as epoxy resin, and redistribution is performed from the electrodes on the semiconductor chip to this expansion portion. Solder beads are also mounted in the expansion portion to ensure the necessary number of terminals. In chip-first fan-out wafer-level packaging or chip-first fan-out panel-level packaging, wiring is arranged across the boundary line formed by the main surface of the semiconductor chip and the main surface of the sealing resin, and a cured film is configured as an insulating film between the wirings.

[0170] The antenna element of the present invention has at least one antenna wiring and the curing film of the present invention. The antenna wiring includes at least one selected from bent loop antennas, coil loop antennas, bent monopole antennas, bent dipole antennas, and microstrip antennas. The proprietary area of ​​an average antenna portion in the antenna wiring is 1000 mm². 2 The cured film is described below as an insulating film that insulates the ground wire from the antenna wiring.

[0171] In one example of the antenna element of the present invention, using Figure 1 Please provide an explanation. Figure 1 This is a schematic diagram of an example of a coplanar powered microstrip antenna, a type of planar antenna. 1a shows a cross-sectional view, and 1b shows a top view. The formation method will be described first. The resin composition of the present invention is coated onto a copper foil and pre-baked. Next, the copper foil is laminated and thermosetting is performed, thereby forming a cured film with copper foil on both sides. Subsequently, a pattern is formed using a subtractive method to obtain a microstrip antenna with… Figure 1 The antenna element is an antenna with a copper wiring pattern of microstrip line (MSL).

[0172] Next, regarding Figure 1The antenna pattern is explained below. In 1a, 15 represents the ground wire (full surface), and 16 represents the insulating film of the substrate forming the antenna. 11 to 13 on the upper layer represent the cross-sections of the antenna wiring obtained by forming the aforementioned pattern. The thickness J of the ground wire wiring and the thickness K of the antenna wiring are arbitrary thicknesses depending on the impedance design, generally ranging from 2 to 20 μm. In 1b, 11 represents the antenna section, 12 represents the matching circuit, 13 represents the MSL power supply line, and 14 represents the power supply point. To achieve impedance integration between the antenna section 11 and the MSL power supply line 13, the length M of the matching circuit 12 has a length of 1 / 4λr (λr = (wavelength of the transmitted radio wave) / (dielectric constant of the insulating material)). 1 / 2 Furthermore, the width W and length L of the antenna section 11 are designed to be 1 / 2λr. The antenna section length L can be set to 1 / 2λr or less depending on the impedance design. By using the curing film of the present invention, a highly reliable antenna element that does not crack after packaging reliability testing can be provided. Furthermore, due to these characteristics, the antenna element using the insulating film of the present invention is suitable as a high-frequency antenna by setting the area of ​​the antenna section (=L×W) to 1000mm². 2 The following dimensions enable the formation of small antenna elements. This results in high-efficiency, high-gain, small-sized antenna elements designed for high frequencies.

[0173] The electronic component of the present invention includes at least a semiconductor package having a semiconductor element, a redistribution layer, a sealing resin, and an antenna wiring, wherein the insulating layer of the redistribution layer and / or the sealing resin contains the cured film of the present invention, preferably the sealing resin is located between the ground wire and the antenna wiring.

[0174] Furthermore, the electronic component of the present invention preferably comprises an antenna element obtained by laminating antenna wiring and the curing film of the present invention, wherein the height of the antenna wiring is 50 to 200 μm and the thickness of the curing film is 80 to 300 μm. By laminating the antenna wiring and the curing film, and setting the height of the antenna wiring and the thickness of the curing film within the above-mentioned ranges, it is possible to transmit and receive over a wide range with a small size. Since the curing film of the present invention exhibits minimal degradation after reliability testing, a highly reliable antenna element that does not crack after reliability testing can be obtained.

[0175] As an example of the aforementioned electronic component, for a semiconductor package having an IC chip (semiconductor element), a redistribution layer, sealing resin, and antenna wiring, the following is used: Figure 2 Please provide an explanation. Figure 2This is a schematic cross-sectional view of a semiconductor package having an IC chip (semiconductor element), a redistribution layer, a sealing resin, and an antenna element. On the electrode pad 202 of the IC chip 201, a redistribution layer (copper layer 2, insulating film layer 3) based on an insulating film 210 is formed by copper wiring 209 and a curing film of the present invention. Barrier metal 211 and solder bumps 212 are formed on the pad of the redistribution layer (copper wiring 209 and insulating film 210). To seal the aforementioned IC chip, a first sealing resin 208 is formed using the curing film of the present invention, and copper wiring 209 serving as a ground line for the antenna is further formed thereon. A first via wiring 207 connecting the ground line 206 and the redistribution layer (copper wiring 209 and insulating film 210) is formed via a via formed within the first sealing resin 208. A second sealing resin 205 based on the curing film of the present invention is formed on the first sealing resin 208 and the ground wiring 206, and a planar antenna wiring 204 is formed thereon. A second via wiring 203 is formed through vias formed within the first sealing resin 208 and the second sealing resin 205, connecting the planar antenna wiring 204 and the redistribution layer (copper wiring 209 and insulating film 210). The average layer thickness of the insulating film 210 is preferably 10–20 μm, and the thickness of the first and second sealing resins is preferably 50–200 μm and 100–400 μm, respectively. The cured film of the present invention exhibits minimal degradation after reliability testing; therefore, a semiconductor package having the obtained antenna element can be obtained that exhibits high reliability without cracking after package reliability testing. Example

[0176] The present invention will be described below by way of examples, but the invention is not limited by these examples. It should be noted that the evaluation of the resin compositions in the examples was performed by the following method. In the evaluation, a resin composition (hereinafter referred to as varnish) that had been pre-filtered with a 1 μm polytetrafluoroethylene filter (manufactured by Sumitomo Electric Industries, Ltd.) was used.

[0177] (1) Evaluation of initial fracture point elongation A varnish was applied to an 8-inch silicon wafer and pre-baked at 120°C for 3 minutes to achieve a film thickness of 11 μm. The coating and pre-baking were then performed using an ACT-8 coating and developing apparatus via spin coating. Following this, an inert oven (CLH-21CD-S, manufactured by Koyo Saichi Systems Co., Ltd.) was used to heat the wafer to 250°C at a rate of 3.5°C / min with an oxygen concentration below 20 ppm, and the wafer was heat-treated at 250°C for 1 hour. When the temperature reached below 50°C, the wafer was removed and immersed in 45% hydrofluoric acid for 1 minute, thereby peeling off the cured film from the wafer. The film was cut into strips 1.5 cm wide and 5 cm long, and stretched at a rate of 5 mm / min using a Tensilon RTM-100 (manufactured by Orientec Co., Ltd.) at room temperature (23.0°C) and humidity (45.0% RH) to determine the elongation at break. The measurement was performed on 10 strips for one sample, and the average of the top 5 points was calculated from the results. The elongation at break was 30% or more as very good (3), 15% or more but less than 30% as good (2), and less than 15% as poor (1).

[0178] (2) Evaluation of the rate of change of elongation at break after reliability testing (High Temperature Storage (HTS)) A clear varnish was applied to an 8-inch silicon wafer using a spin-coating method, achieving a film thickness of 11 μm after pre-baking at 120°C for 3 minutes. Following this initial coating and pre-baking, an ACT-8 coating and developing apparatus was used. The wafer was then heat-treated in an inert oven (CLH-21CD-S, manufactured by Koyo Saichi Systems Co., Ltd.) at an oxygen concentration below 20 ppm, with the temperature increased to 250°C at a rate of 3.5°C / min, and maintained at 250°C for 1 hour. Once the temperature dropped below 50°C, the wafer was removed, and the wafer with the cured film was placed in an oven (Clean Oven DE42, manufactured by Yamato Science) for heat treatment at 175°C for 200 hours under atmospheric conditions. After heat treatment, the wafer was removed and immersed in 45% hydrofluoric acid for 1 minute, thereby peeling off the cured film from the wafer. The film was cut into short strips with a width of 1.5 cm and a length of 5 cm. Using a tensilon RTM-100 (manufactured by ORIENTEC Co., Ltd.), the film was stretched at a stretching speed of 5 mm / min at a room temperature of 23.0 °C and a humidity of 45.0% RH to determine the elongation at break. The test was performed on 10 strips for one sample. The average value of the top 5 points was calculated and recorded as the elongation at break (%) after HTS. The change rate of elongation at break after reliability test (HTS) was defined as |(elongation at break of cured film after reliability test) - (initial elongation at break)| × 100 / (elongation at break of cured film after reliability test). The change rate of elongation at break after reliability test (HTS) was less than 10% and recorded as very good (3), more than 10% and less than 30% and recorded as good (2), and more than 30% and recorded as poor (1).

[0179] (3) Crack resistance evaluation When performing stripping evaluation using copper interconnects, prepare the following evaluation substrate. On an 8-inch silicon wafer, fabricate cylindrical copper interconnects with a thickness of 5 μm and a diameter of 90 μm, spaced evenly at 150 μm center-to-center distances. Use this substrate as the evaluation substrate.

[0180] A clear varnish was applied to the aforementioned evaluation substrate, and a pre-baked film was prepared by spin coating using an ACT-8 coating and developing apparatus (manufactured by Tokyo Electron Co., Ltd.) to achieve a film thickness of 8-12 μm after heat treatment at 120°C for 3 minutes. Pre-baking was performed at 120°C for 3 minutes in all cases.

[0181] When the resin composition is not photosensitive, the resulting pre-baked film is heated in an inert oven (manufactured by Koyo Service Corporation, CLH-21CD-S) at an oxygen concentration of less than 20 ppm under a nitrogen flow, from 50°C to 250°C at a rate of 3.5°C / min, and then heat-treated at 250°C for 1 hour to obtain a cured film. The resulting cured film is then subjected to a carbon dioxide laser (wavelength 10600 nm) at a rate of 600 mJ / cm². 2 The irradiation dose forms a 50μm circular opening pattern on the cylindrical copper wire, resulting in a patterned film.

[0182] When the resin composition is photosensitive, the resulting pre-baked film is exposed using an i-line stepper (Nicon Inc., NSR-2005i9C) with a mask capable of forming a 50μm circular opening pattern on cylindrical copper wiring, at 800mJ / cm². 2 Exposure will be based on the amount of exposure.

[0183] After exposure, development was performed using a 2.38% by mass tetramethylammonium (TMAH) aqueous solution (manufactured by Tama Chemical Industry) or cyclopentanone, with the film thickness change of the unexposed area before and after development reaching 1.5 μm. Then, the film was rinsed with pure water or propylene glycol monomethyl ether acetate and dried. Subsequently, the patterned film was heat-treated in an inert oven (manufactured by Koyo Saichi Moshisetsu Co., Ltd., CLH-21CD-S) under a nitrogen flow with an oxygen concentration of less than 20 ppm, from 50°C to 250°C at a rate of 3.5°C / min, and then heat-treated at 250°C for 1 hour to cure the patterned film, thus obtaining a cured film. It should be noted that the film thickness of the patterned film after pre-baking and development was measured using a Lamdaes STM-602 optical interferometric film thickness measuring device manufactured by Dai Nippon Screen Co., Ltd., with a refractive index of 1.629. The film thickness of the cured film was measured at a refractive index of 1.773.

[0184] Next, the patterned sample (hereinafter referred to as the sample) was placed in a thermal cycling test chamber (conditions: -65℃ / 30min~150℃ / 30min) for 200 cycles. Afterwards, the sample was removed, and the presence of cracks in the cured film was observed using an optical microscope. Ten locations were observed: two at the center of the substrate and two at each of the four ends, for a total of 10 locations. A crack count of 0 was recorded as "extremely good" (4), 1-2 as "good" (3), 3-4 as "slightly poor" (2), and 5-10 as "poor" (1). The fewer the crack count, the better the crack resistance.

[0185] (4) Pattern processing properties (4)-1 Sensitivity After spin-coating a varnish onto a silicon wafer using a spin coater, a pre-baked film with a thickness of 11 μm was prepared by pre-baking at 120°C for 3 minutes using a heated plate. On the resulting pre-baked film, a parallel light mask aligner (hereinafter referred to as PLA) (Canon Corporation PLA-501F) was used with an ultra-high pressure mercury lamp as the light source, and contact exposure was performed through a grayscale mask (a pattern with 1:1 line spacing and 1-50 μm) for sensitivity measurement. After exposure and baking at 120°C for 1 minute, a MARK-7 coating and developing apparatus was used. For negative films that are insoluble in alkaline aqueous solutions, cyclopentanone was used as the developer for 2 minutes of spray development, followed by a 30-second rinse with propylene glycol monomethyl ether acetate. For negative or positive films that are soluble in alkaline aqueous solutions, a 90-second water-pit development was performed using a 2.38% by mass TMAH aqueous solution, followed by a 30-second rinse with water.

[0186] After development, the film thickness is measured. In negative mode, the minimum exposure amount with a residual film rate of more than 90% in the exposed area is used as the sensitivity (mJ / cm). 2 In the positive case, the minimum exposure amount required for the film thickness of the exposed area to reach 5 nm or less (below the detection limit) is used as the sensitivity. The exposure amount is measured using an I-line illuminance meter.

[0187] (4)-2 resolution The minimum pattern size (μm) after development was determined at the exposure level defined in (4)-1.

[0188] <Example of monomer synthesis> The monomers with the following structures used in this invention are described in Journal of Fluorine Chemistry 130 (2009) 573-580. They were obtained by reacting 4-iodoaniline, 2-amino-4-iodophenol, and 4-iodobenzoic acid to obtain monomers (X), (Y), and (Z), respectively.

[0189] [Chemistry 17]

[0190] <Synthetic Example 1: Synthesis of Polyimide Precursor (A-1)> Under a dry nitrogen atmosphere, 6.20 g (0.02 mol) of 4,4′-oxophthalic anhydride (hereinafter referred to as ODPA) was dissolved in 100 g of N-methyl-2-pyrrolidone (hereinafter referred to as NMP). Then, 6.01 g (0.0164 mol) of 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane (hereinafter referred to as BAHF), 0.77 g (0.0016 mol) of monomer (X), and 25 g of NMP were added together, and the reaction was carried out at 20°C for 1 hour, followed by a reaction at 50°C for 2 hours. Next, 0.44 g (0.004 mol) of 3-aminophenol (manufactured by Tokyo Chemical Industry Co., Ltd.) was added, and the reaction was carried out at 50°C for 2 hours. Subsequently, a solution obtained by diluting 7.15 g (0.06 mol) of N,N-dimethylformamide dimethyl acetal (hereinafter referred to as DFA) with 10 g of NMP was added dropwise over 10 minutes. After the addition, the mixture was stirred at 50 °C for 3 hours. After the reaction was completed, the solution was added to 1 L of water, and the polymer solid precipitate was collected by filtration. The polymer solid was dried in a vacuum dryer at 80 °C for 20 hours to obtain polymer (A-1) (polyamic acid ester).

[0191] <Synthetic Example 2: Synthesis of Polyimide Precursor (A-2)> Under a dry nitrogen stream, 6.20 g (0.02 mol) of ODPA was dissolved in 100 g of NMP. Then, 5.49 g (0.015 mol) of BAHF, 1.45 g (0.003 mol) of monomer (X), and 25 g of NMP were added together, and the reaction was carried out at 20 °C for 1 hour, followed by a reaction at 50 °C for 2 hours. Next, 0.44 g (0.004 mol) of 3-aminophenol was added, and the reaction was carried out at 50 °C for 2 hours. Subsequently, a solution obtained by diluting 7.15 g (0.06 mol) of DFA with 10 g of NMP was added dropwise over 10 minutes. After the addition, the mixture was stirred at 50 °C for 3 hours. After the reaction was complete, the solution was added to 1 L of water, and the polymer solid precipitate was collected by filtration. The polymer solid was dried in a vacuum dryer at 80 °C for 20 hours to obtain polymer (A-2) (polyamic acid ester).

[0192] <Synthetic Example 3: Synthesis of Polyimide Precursor (A-3)> Under a dry nitrogen stream, 6.20 g (0.02 mol) of ODPA was dissolved in 100 g of NMP. Then, 4.25 g (0.0116 mol) of BAHF, 3.10 g (0.0064 mol) of monomer (X), and 25 g of NMP were added together, and the reaction was carried out at 20 °C for 1 hour, followed by 2 hours at 50 °C. Next, 0.44 g (0.004 mol) of 3-aminophenol was added, and the reaction was carried out at 50 °C for 2 hours. Subsequently, a solution obtained by diluting 7.15 g (0.06 mol) of DFA with 10 g of NMP was added dropwise over 10 minutes. After the addition, the mixture was stirred at 50 °C for 3 hours. After the reaction was complete, the solution was added to 1 L of water, and the polymer solid precipitate was collected by filtration. The polymer solid was dried in a vacuum dryer at 80 °C for 20 hours to obtain polymer (A-3) (polyamic acid ester).

[0193] <Synthetic Example 4: Synthesis of Polyimide Precursor (A-4)> Under a dry nitrogen stream, 6.20 g (0.02 mol) of ODPA was dissolved in 100 g of NMP. Then, 3.08 g (0.0084 mol) of BAHF, 4.65 g (0.0096 mol) of monomer (X), and 25 g of NMP were added together, and the reaction was carried out at 20 °C for 1 hour, followed by a reaction at 50 °C for 2 hours. Next, 0.44 g (0.004 mol) of 3-aminophenol was added, and the reaction was carried out at 50 °C for 2 hours. Subsequently, a solution obtained by diluting 7.15 g (0.06 mol) of DFA with 10 g of NMP was added dropwise over 10 minutes. After the addition, the mixture was stirred at 50 °C for 3 hours. After the reaction was complete, the solution was added to 1 L of water, and the polymer solid precipitate was collected by filtration. The polymer solid was dried in a vacuum dryer at 80 °C for 20 hours to obtain polymer (A-4) (polyamic acid ester).

[0194] <Synthetic Example 5: Synthesis of Polyimide Precursor (A-5)> Under a dry nitrogen stream, 6.20 g (0.02 mol) of ODPA was dissolved in 100 g of NMP. Then, 1.90 g (0.0052 mol) of BAHF, 6.20 g (0.0128 mol) of monomer (X), and 25 g of NMP were added together, and the reaction was carried out at 20 °C for 1 hour, followed by a reaction at 50 °C for 2 hours. Next, 0.44 g (0.004 mol) of 3-aminophenol was added, and the reaction was carried out at 50 °C for 2 hours. Subsequently, a solution obtained by diluting 7.15 g (0.06 mol) of DFA with 10 g of NMP was added dropwise over 10 minutes. After the addition, the mixture was stirred at 50 °C for 3 hours. After the reaction was complete, the solution was added to 1 L of water, and the polymer solid precipitate was collected by filtration. The polymer solid was dried in a vacuum dryer at 80 °C for 20 hours to obtain polymer (A-5) (polyamic acid ester).

[0195] <Synthetic Example 6: Synthesis of Polyimide Precursor (A-6)> Under a dry nitrogen stream, 6.20 g (0.02 mol) of ODPA was dissolved in 100 g of NMP. 8.72 g (0.018 mol) of monomer (X) was added together with 25 g of NMP, and the reaction was carried out at 20 °C for 1 hour, followed by 2 hours at 50 °C. Next, 0.44 g (0.004 mol) of 3-aminophenol was added, and the reaction was carried out at 50 °C for 2 hours. Subsequently, a solution obtained by diluting 7.15 g (0.06 mol) of DFA with 10 g of NMP was added dropwise over 10 minutes. After the addition, the mixture was stirred at 50 °C for 3 hours. After the reaction was complete, the solution was added to 1 L of water, and the polymer solid precipitate was collected by filtration. The polymer solid was dried in a vacuum dryer at 80 °C for 20 hours to obtain polymer (A-6) (polyamic acid ester).

[0196] <Synthesis Example 7: Synthesis of Polyimide (A-7)> Under a dry nitrogen stream, 5.86 g (0.016 mol) of BAHF, 31.0 g (0.064 mol) of monomer (X), 1.24 g (0.005 mol) of 1,3-bis(3-aminopropyl)tetramethyldisiloxane (hereinafter referred to as SiDA), and 3.27 g (0.03 mol) of 3-aminophenol were dissolved in 180 g of NMP. Then, 31.02 g (0.1 mol) of ODPA was added together with 20 g of NMP, and the mixture was reacted at 60 °C for 1 hour, followed by stirring at 180 °C for 4 hours. After stirring, the solution was added to 3 L of water, yielding a white precipitate. The precipitate was collected by filtration, washed three times with water, and dried in a vacuum dryer at 80 °C for 20 hours to obtain polyimide (A-7) powder.

[0197] <Synthetic Example 8: Synthesis of Polyhydroxyamide (A-8)> Under a dry nitrogen stream, 100 g of NMP was added, along with BAHF (4.76 g, 0.013 mol), monomer (X) (15.5 g, 0.032 mol), and 3-aminophenol (1.09 g, 0.010 mol). After dissolving by stirring at room temperature, the reaction solution was kept at -10 to 0 °C. Simultaneously, 4,4′-diphenyl ether dicarboxylic acid chloride (14.76 g, 0.05 mol) was added, and the mixture was stirred continuously at room temperature for 3 hours. The reaction solution was then added to 3 liters of water, and the precipitate was recovered. After washing three times with pure water, the precipitate was dried in a vacuum dryer at 80 °C for 20 hours to obtain polyhydroxyamide (A-8) powder.

[0198] <Synthetic Example 9: Synthesis of Polyimide Precursor (A-9)> Under a dry nitrogen stream, 6.20 g (0.02 mol) of ODPA was dissolved in 100 g of NMP. Then, 1.69 g (0.015 mol) of 1,4-phenylenediamine (hereinafter referred to as PDA), 1.45 g (0.003 mol) of monomer (X), and 25 g of NMP were added together, and the reaction was carried out at 20 °C for 1 hour, followed by a reaction at 50 °C for 2 hours. Next, 0.44 g (0.004 mol) of 3-aminophenol was added, and the reaction was carried out at 50 °C for 2 hours. Subsequently, a solution obtained by diluting 7.15 g (0.06 mol) of DFA with 10 g of NMP was added dropwise over 10 minutes. After the addition, the mixture was stirred at 50 °C for 3 hours. After the reaction was complete, the solution was added to 1 L of water, and the polymer solid precipitate was collected by filtration. The polymer solid was dried in a vacuum dryer at 80 °C for 20 hours to obtain polymer (A-9) (polyamic acid ester).

[0199] <Synthetic Example 10: Synthesis of Polyimide Precursor (A-10)> Under a dry nitrogen stream, 6.20 g (0.02 mol) of ODPA was dissolved in 100 g of NMP. Then, 1.10 g (0.003 mol) of BAHF, 1.30 g (0.012 mol) of PDA, 1.45 g (0.003 mol) of monomer (X) and 25 g of NMP were added together, and the reaction was carried out at 20 °C for 1 hour, followed by a reaction at 50 °C for 2 hours. Next, 0.44 g (0.004 mol) of 3-aminophenol was added, and the reaction was carried out at 50 °C for 2 hours. Subsequently, a solution obtained by diluting 7.15 g (0.06 mol) of DFA with 10 g of NMP was added dropwise over 10 minutes. After the addition, the mixture was stirred at 50 °C for 3 hours. After the reaction was complete, the solution was added to 1 L of water, and the polymer solid precipitate was collected by filtration. The polymer solid was dried in a vacuum dryer at 80 °C for 20 hours to obtain polymer (A-10) (polyamic acid ester).

[0200] <Synthetic Example 11: Synthesis of Polyimide Precursor (A-11)> Under a dry nitrogen stream, 6.20 g (0.02 mol) of ODPA was dissolved in 100 g of NMP. Then, 2.20 g (0.006 mol) of BAHF, 0.97 g (0.009 mol) of PDA, 1.45 g (0.003 mol) of monomer (X) and 25 g of NMP were added together, and the reaction was carried out at 20 °C for 1 hour, followed by 2 hours at 50 °C. Next, 0.44 g (0.004 mol) of 3-aminophenol was added, and the reaction was carried out at 50 °C for 2 hours. Subsequently, a solution obtained by diluting 7.15 g (0.06 mol) of DFA with 10 g of NMP was added dropwise over 10 minutes. After the addition, the mixture was stirred at 50 °C for 3 hours. After the reaction was complete, the solution was added to 1 L of water, and the polymer solid precipitate was collected by filtration. The polymer solid was dried in a vacuum dryer at 80 °C for 20 hours to obtain polymer (A-11) (polyamic acid ester).

[0201] <Synthetic Example 12: Synthesis of Polyimide Precursor (A-12)> Under a dry nitrogen stream, 6.20 g (0.02 mol) of ODPA was dissolved in 100 g of NMP. Then, 0.97 g (0.009 mol) of PDA, 4.36 g (0.009 mol) of monomer (X), and 25 g of NMP were added together, and the reaction was carried out at 20 °C for 1 hour, followed by a reaction at 50 °C for 2 hours. Next, 0.44 g (0.004 mol) of 3-aminophenol was added, and the reaction was carried out at 50 °C for 2 hours. Subsequently, a solution obtained by diluting 7.15 g (0.06 mol) of DFA with 10 g of NMP was added dropwise over 10 minutes. After the addition, the mixture was stirred at 50 °C for 3 hours. After the reaction was complete, the solution was added to 1 L of water, and the polymer solid precipitate was collected by filtration. The polymer solid was dried in a vacuum dryer at 80 °C for 20 hours to obtain polymer (A-12) (polyamic acid ester).

[0202] <Synthetic Example 13: Synthesis of Polyimide Precursor (A-13)> Under a dry nitrogen stream, 6.20 g (0.02 mol) of ODPA was dissolved in 100 g of NMP. Then, 2.20 g (0.006 mol) of BAHF, 2.88 g (0.009 mol) of 2,2′-bis(trifluoromethyl)benzidine (hereinafter referred to as TFMB), 1.45 g (0.003 mol) of monomer (X) and 25 g of NMP were added together, and the reaction was carried out at 20 °C for 1 hour, followed by a reaction at 50 °C for 2 hours. Next, 0.44 g (0.004 mol) of 3-aminophenol was added, and the reaction was carried out at 50 °C for 2 hours. Subsequently, a solution obtained by diluting 7.15 g (0.06 mol) of DFA with 10 g of NMP was added dropwise over 10 minutes. After the addition, the mixture was stirred at 50 °C for 3 hours. After the reaction was completed, the solution was added to 1 L of water, and the polymer solid precipitate was collected by filtration. The polymer solid was dried in a vacuum dryer at 80°C for 20 hours to obtain polymer (A-13) (polyamic acid ester).

[0203] <Synthetic Example 14: Synthesis of Polyimide Precursor (A-14)> Under a dry nitrogen stream, 6.20 g (0.02 mol) of ODPA was dissolved in 100 g of NMP. Then, 2.20 g (0.006 mol) of BAHF, 1.42 g (0.009 mol) of 1,5-diaminonaphthalene, 1.45 g (0.003 mol) of monomer (X) and 25 g of NMP were added together, and the reaction was carried out at 20 °C for 1 hour, followed by 2 hours at 50 °C. Next, 0.44 g (0.004 mol) of 3-aminophenol was added, and the reaction was carried out at 50 °C for 2 hours. Subsequently, a solution obtained by diluting 7.15 g (0.06 mol) of DFA with 10 g of NMP was added dropwise over 10 minutes. After the addition, the mixture was stirred at 50 °C for 3 hours. After the reaction was complete, the solution was added to 1 L of water, and the polymer solid precipitate was collected by filtration. The polymer solid was dried in a vacuum dryer at 80°C for 20 hours to obtain polymer (A-14) (polyamic acid ester).

[0204] <Synthesis Example 15: Synthesis of Polyimide (A-15)> Under a dry nitrogen stream, 12.81 g (0.04 mol) of TFMB, 19.37 g (0.04 mol) of monomer (X), 1.24 g (0.005 mol) of SiDA, and 3.27 g (0.03 mol) of 3-aminophenol were dissolved in 180 g of NMP. Then, 31.02 g (0.1 mol) of ODPA and 20 g of NMP were added together, and the mixture was reacted at 60 °C for 1 hour, followed by stirring at 180 °C for 4 hours. After stirring, the solution was added to 3 L of water, yielding a white precipitate. The precipitate was collected by filtration, washed three times with water, and dried in a vacuum dryer at 80 °C for 20 hours to obtain polyimide (A-15) powder.

[0205] <Synthetic Example 16: Synthesis of Polyhydroxyamide (A-16)> Under a dry nitrogen stream, 100 g of NMP was added, along with 7.20 g (0.0225 mol) of TFMB, monomer (X) (10.9 g (0.0225 mol), and 3-aminophenol (1.09 g (0.010 mol)). After dissolving by stirring at room temperature, the reaction solution was maintained at -10 to 0 °C. Simultaneously, 14.76 g (0.05 mol) of 4,4′-diphenyl ether dicarboxylic acid chloride was added, and the mixture was stirred continuously at room temperature for 3 hours. The reaction solution was then added to 3 liters of water, and the precipitate was recovered. After washing three times with pure water, the precipitate was dried in a vacuum dryer at 80 °C for 20 hours to obtain polyhydroxyamide (A-16) powder.

[0206] <Synthetic Example 17: Synthesis of Polyimide Precursor (A-17)> Under a dry nitrogen stream, 6.20 g (0.02 mol) of ODPA was dissolved in 100 g of NMP. Then, 5.27 g (0.0144 mol) of BAHF, 0.77 g (0.0016 mol) of monomer (X), and 25 g of NMP were added together, and the reaction was carried out at 20 °C for 1 hour, followed by a reaction at 50 °C for 2 hours. Next, 0.87 g (0.008 mol) of 3-aminophenol was added, and the reaction was carried out at 50 °C for 2 hours. Subsequently, a solution obtained by diluting 7.15 g (0.06 mol) of DFA with 10 g of NMP was added dropwise over 10 minutes. After the addition, the mixture was stirred at 50 °C for 3 hours. After the reaction was complete, the solution was added to 1 L of water, and the polymer solid precipitate was collected by filtration. The polymer solid was dried in a vacuum dryer at 80 °C for 20 hours to obtain polymer (A-17) (polyamic acid ester).

[0207] <Synthetic Example 18: Synthesis of Polyimide Precursor (A-18)> Under a dry nitrogen stream, 5.88 g (0.02 mol) of 3,3′,4,4′-biphenyltetracarboxylic dianhydride (hereinafter referred to as BPDA) was dissolved in 100 g of NMP. Then, 5.27 g (0.0144 mol) of BAHF, 0.77 g (0.0016 mol) of monomer (X), and 25 g of NMP were added together, and the reaction was carried out at 20 °C for 1 hour, followed by a reaction at 50 °C for 2 hours. Next, 0.87 g (0.008 mol) of 4-aminophenol was added, and the reaction was carried out at 50 °C for 2 hours. Subsequently, a solution obtained by diluting 7.15 g (0.06 mol) of DFA with 10 g of NMP was added dropwise over 10 minutes. After the addition, the mixture was stirred at 50 °C for 3 hours. After the reaction was completed, the solution was added to 1 L of water, and the polymer solid precipitate was collected by filtration. The polymer solid was dried in a vacuum dryer at 80°C for 20 hours to obtain polymer (A-18) (polyamic acid ester).

[0208] <Synthetic Example 19: Synthesis of Polyimide Precursor (A-19)> Under a dry nitrogen atmosphere, 8.88 g (0.02 mol) of 4,4′-(hexafluoroisopropylidene) phthalic anhydride (hereinafter referred to as 6FDA) was dissolved in 100 g of NMP. Then, 5.27 g (0.0144 mol) of BAHF, 0.77 g (0.0016 mol) of monomer (X), and 25 g of NMP were added together, and the reaction was carried out at 20 °C for 1 hour, followed by a reaction at 50 °C for 2 hours. Next, 0.87 g (0.008 mol) of 4-aminophenol was added, and the reaction was carried out at 50 °C for 2 hours. Subsequently, a solution obtained by diluting 7.15 g (0.06 mol) of DFA with 10 g of NMP was added dropwise over 10 minutes. After the addition, the mixture was stirred at 50 °C for 3 hours. After the reaction was completed, the solution was added to 1 L of water, and the polymer solid precipitate was collected by filtration. The polymer solid was dried in a vacuum dryer at 80°C for 20 hours to obtain polymer (A-19) (polyamic acid ester).

[0209] <Synthetic Example 20: Synthesis of Polyimide Precursor (A-20)> Under a dry nitrogen stream, 6.20 g (0.02 mol) of ODPA was dissolved in 100 g of NMP. Then, 4.69 g (0.0128 mol) of BAHF, 1.55 g (0.0032 mol) of monomer (X), and 25 g of NMP were added together, and the reaction was carried out at 20 °C for 1 hour, followed by a reaction at 50 °C for 2 hours. Next, 0.87 g (0.008 mol) of 3-aminophenol was added, and the reaction was carried out at 50 °C for 2 hours. Subsequently, a solution obtained by diluting 7.15 g (0.06 mol) of DFA with 10 g of NMP was added dropwise over 10 minutes. After the addition, the mixture was stirred at 50 °C for 3 hours. After the reaction was complete, the solution was added to 1 L of water, and the polymer solid precipitate was collected by filtration. The polymer solid was dried in a vacuum dryer at 80 °C for 20 hours to obtain polymer (A-20) (polyamic acid ester).

[0210] <Synthetic Example 21: Synthesis of Polyimide Precursor (A-21)> Under a dry nitrogen stream, 5.88 g (0.02 mol) of BPDA was dissolved in 100 g of NMP. Then, 4.69 g (0.0128 mol) of BAHF, 1.55 g (0.0032 mol) of monomer (X), and 25 g of NMP were added together, and the reaction was carried out at 20 °C for 1 hour, followed by a reaction at 50 °C for 2 hours. Next, 0.87 g (0.008 mol) of 4-aminophenol was added, and the reaction was carried out at 50 °C for 2 hours. Subsequently, a solution obtained by diluting 7.15 g (0.06 mol) of DFA with 10 g of NMP was added dropwise over 10 minutes. After the addition, the mixture was stirred at 50 °C for 3 hours. After the reaction was complete, the solution was added to 1 L of water, and the polymer solid precipitate was collected by filtration. The polymer solid was dried in a vacuum dryer at 80 °C for 20 hours to obtain polymer (A-21) (polyamic acid ester).

[0211] <Synthetic Example 22: Synthesis of Polyimide Precursor (A-22)> Under a dry nitrogen stream, 8.88 g (0.02 mol) of 6FDA was dissolved in 100 g of NMP. Then, 4.69 g (0.0128 mol) of BAHF, 1.55 g (0.0032 mol) of monomer (X), and 25 g of NMP were added together, and the reaction was carried out at 20°C for 1 hour, followed by 2 hours at 50°C. Next, 0.87 g (0.008 mol) of 4-aminophenol was added, and the reaction was carried out at 50°C for 2 hours. Subsequently, a solution obtained by diluting 7.15 g (0.06 mol) of DFA with 10 g of NMP was added dropwise over 10 minutes. After the addition, the mixture was stirred at 50°C for 3 hours. After the reaction was complete, the solution was added to 1 L of water, and the polymer solid precipitate was collected by filtration. The polymer solid was dried in a vacuum dryer at 80°C for 20 hours to obtain polymer (A-22) (polyamic acid ester).

[0212] <Synthesis Example 23: Synthesis of Polyimide (A-23)> Under a dry nitrogen stream, 26.37 g (0.072 mol) of BAHF, 3.87 g (0.008 mol) of monomer (X), 1.24 g (0.005 mol) of 1,3-bis(3-aminopropyl)tetramethyldisiloxane (hereinafter referred to as SiDA), and 3.27 g (0.03 mol) of 3-aminophenol were dissolved in 180 g of NMP. Then, 1.02 g (0.1 mol) of ODPA was added together with 20 g of NMP, and the mixture was reacted at 60 °C for 1 hour, followed by stirring at 180 °C for 4 hours. After stirring, the solution was added to 3 L of water, yielding a white precipitate. The precipitate was collected by filtration, washed three times with water, and dried in a vacuum dryer at 80 °C for 20 hours to obtain polyimide (A-23) powder.

[0213] <Synthesis Example 24: Synthesis of Polyimide (A-24)> Under a dry nitrogen stream, 26.37 g (0.072 mol) of BAHF, 3.87 g (0.008 mol) of monomer (X), 1.24 g (0.005 mol) of SiDA, and 3.27 g (0.03 mol) of 3-aminophenol were dissolved in 180 g of NMP. Then, 29.42 g (0.1 mol) of BPDA and 20 g of NMP were added together, and the mixture was reacted at 60 °C for 1 hour, followed by stirring at 180 °C for 4 hours. After stirring, the solution was added to 3 L of water, yielding a white precipitate. The precipitate was collected by filtration, washed three times with water, and dried in a vacuum dryer at 80 °C for 20 hours to obtain polyimide (A-24) powder.

[0214] <Synthesis Example 25: Synthesis of Polyimide (A-25)> Under a dry nitrogen stream, 26.37 g (0.072 mol) of BAHF, 3.87 g (0.008 mol) of monomer (X), 1.24 g (0.005 mol) of SiDA, and 3.27 g (0.03 mol) of 3-aminophenol were dissolved in 180 g of NMP. Then, 44.42 g (0.1 mol) of 6FDA was added together with 20 g of NMP, and the mixture was reacted at 60 °C for 1 hour, followed by stirring at 180 °C for 4 hours. After stirring, the solution was added to 3 L of water, yielding a white precipitate. The precipitate was collected by filtration, washed three times with water, and dried in a vacuum dryer at 80 °C for 20 hours to obtain polyimide (A-25) powder.

[0215] <Synthetic Example 26: Synthesis of Polyimide Precursor (A-26)> Under a dry nitrogen stream, 6.20 g (0.02 mol) of ODPA was dissolved in 100 g of NMP. Then, 2.93 g (0.008 mol) of BAHF, 4.13 g (0.008 mol) of monomer (Y), and 25 g of NMP were added together, and the reaction was carried out at 20 °C for 1 hour, followed by a reaction at 50 °C for 2 hours. Next, 0.87 g (0.008 mol) of 3-aminophenol was added, and the reaction was carried out at 50 °C for 2 hours. Subsequently, a solution obtained by diluting 7.15 g (0.06 mol) of DFA with 10 g of NMP was added dropwise over 10 minutes. After the addition, the mixture was stirred at 50 °C for 3 hours. After the reaction was complete, the solution was added to 1 L of water, and the polymer solid precipitate was collected by filtration. The polymer solid was dried in a vacuum dryer at 80 °C for 20 hours to obtain polymer (A-26) (polyamic acid ester).

[0216] <Synthetic Example 27: Synthesis of Polyimide Precursor (A-27)> Under a dry nitrogen stream, 6.20 g (0.02 mol) of ODPA was dissolved in 100 g of NMP. 8.26 g (0.016 mol) of monomer (Y) was added together with 25 g of NMP, and the reaction was carried out at 20 °C for 1 hour, followed by 2 hours at 50 °C. Next, 0.87 g (0.008 mol) of 3-aminophenol was added, and the reaction was carried out at 50 °C for 2 hours. Subsequently, a solution obtained by diluting 7.15 g (0.06 mol) of DFA with 10 g of NMP was added dropwise over 10 minutes. After the addition, the mixture was stirred at 50 °C for 3 hours. After the reaction was complete, the solution was added to 1 L of water, and the polymer solid precipitate was collected by filtration. The polymer solid was dried in a vacuum dryer at 80 °C for 20 hours to obtain polymer (A-27) (polyamic acid ester).

[0217] <Synthesis Example 28: Synthesis of Polyimide (A-28)> Under a dry nitrogen stream, 14.65 g (0.04 mol) of BAHF, 20.68 g (0.04 mol) of monomer (Y), 1.24 g (0.005 mol) of SiDA, and 3.27 g (0.03 mol) of 3-aminophenol were dissolved in 180 g of NMP. Then, 1.02 g (0.1 mol) of ODPA and 20 g of NMP were added together, and the mixture was reacted at 60 °C for 1 hour, followed by stirring at 180 °C for 4 hours. After stirring, the solution was added to 3 L of water, yielding a white precipitate. The precipitate was collected by filtration, washed three times with water, and dried in a vacuum dryer at 80 °C for 20 hours to obtain polyimide (A-28) powder.

[0218] <Synthesis Example 29: Synthesis of Polyimide (A-29)> Under a dry nitrogen stream, 41.30 g (0.08 mol) of monomer (Y), 1.24 g (0.005 mol) of SiDA, and 3.27 g (0.03 mol) of 3-aminophenol were dissolved in 180 g of NMP. Then, 31.02 g (0.1 mol) of ODPA and 20 g of NMP were added together, and the mixture was reacted at 60 °C for 1 hour, followed by stirring at 180 °C for 4 hours. After stirring, the solution was added to 3 L of water, yielding a white precipitate. The precipitate was collected by filtration, washed three times with water, and dried in a vacuum dryer at 80 °C for 20 hours to obtain polyimide (A-29) powder.

[0219] <Synthetic Example 30: Synthesis of Polyhydroxyamide (A-30)> Under a dry nitrogen stream, 100 g of NMP was added, along with BAHF (14.83 g, 0.0405 mol), monomer (X) (2.18 g, 0.0045 mol), and 3-aminophenol (1.09 g, 0.010 mol). After dissolving by stirring at room temperature, the reaction solution was kept at -10 to 0 °C. Simultaneously, 4,4′-diphenyl ether dicarboxylic acid chloride (14.76 g, 0.05 mol) was added, and the mixture was stirred continuously at room temperature for 3 hours. The reaction solution was then added to 3 liters of water, and the precipitate was recovered. After washing three times with pure water, the precipitate was dried in a vacuum dryer at 80 °C for 20 hours to obtain polyhydroxyamide (A-30) powder.

[0220] <Synthetic Example 31: Synthesis of Polyhydroxyamide (A-31)> Under a dry nitrogen stream, 100 g of NMP was added, along with BAHF (13.19 g, 0.036 mol), monomer (X) (4.36 g, 0.009 mol), and 3-aminophenol (1.09 g, 0.010 mol). After dissolving by stirring at room temperature, the reaction solution was kept at -10 to 0 °C. Simultaneously, 4,4′-diphenyl ether dicarboxylic acid chloride (14.76 g, 0.05 mol) was added, and the mixture was stirred continuously at room temperature for 3 hours. The reaction solution was then added to 3 liters of water, and the precipitate was recovered. After washing three times with pure water, the precipitate was dried in a vacuum dryer at 80 °C for 20 hours to obtain polyhydroxyamide (A-31) powder.

[0221] Synthesis Example 32: Synthesis of Polyhydroxyamide (A-32) Under a dry nitrogen stream, 100 g of NMP was added, along with 8.24 g of BAHF (0.0225 mol), monomer (Y) (11.61 g, 0.0225 mol), and 3-aminophenol (1.09 g, 0.010 mol). After dissolving by stirring at room temperature, the reaction solution was kept at -10 to 0 °C. Simultaneously, 14.76 g of 4,4′-diphenyl ether dicarboxylic acid chloride (0.05 mol) was added, and the mixture was stirred continuously at room temperature for 3 hours. The reaction solution was then added to 3 liters of water, and the precipitate was recovered. After washing three times with pure water, the precipitate was dried in a vacuum dryer at 80 °C for 20 hours to obtain polyhydroxyamide (A-32) powder.

[0222] <Synthetic Example 33: Synthesis of Polyhydroxyamide (A-33)> Under a dry nitrogen stream, 100 g of NMP was added, along with monomer (Y) (23.23 g, 0.045 mol) and 3-aminophenol (1.09 g, 0.010 mol). After dissolving by stirring at room temperature, the reaction solution was maintained at -10 to 0 °C. Simultaneously, 4,4′-diphenyl ether dicarboxylic acid chloride (14.76 g, 0.05 mol) was added, and the mixture was stirred continuously at room temperature for 3 hours. The reaction solution was then added to 3 liters of water, and the precipitate was recovered. After washing three times with pure water, the precipitate was dried in a vacuum dryer at 80 °C for 20 hours to obtain polyhydroxyamide (A-33) powder.

[0223] <Synthetic Example 34: Synthesis of Polyhydroxyamide (A-34)> Under a dry nitrogen gas flow, 100 g of NMP and monomer (Z) (27.11 g, 0.05 mol) were added and stirred until dissolved at room temperature. The mixture was then cooled to 0°C. Thionyl chloride (12.49 g, 0.105 mol) was added dropwise while maintaining the reaction temperature below 10°C. After the addition was complete, the mixture was stirred at around 10°C for 30 minutes to obtain a carboxylic acid acyl chloride solution of monomer Z. Next, 100 g of NMP, 16.48 g of BAHF (0.045 mol), and 3-aminophenol (1.09 g, 0.010 mol) were added and stirred until dissolved. Then, pyridine (17.40 g, 0.22 mol) was added. The solution was cooled to 0°C and maintained below 10°C while the carboxylic acid acyl chloride solution of monomer Z was added dropwise. The mixture was stirred for 30 minutes, and then stirred at room temperature for another 30 minutes. The reaction solution was added to 3 liters of water, the precipitate was recovered, washed three times with pure water, and then dried in a vacuum dryer at 80°C for 20 hours to obtain polyhydroxyamide (A-34) powder.

[0224] <Synthetic Example 35: Synthesis of Polyimide Precursor (A-35)> 31.02 g (0.10 mol) of ODPA was added to a 500 mL separable flask, along with 26.03 g (0.20 mol) of 2-hydroxyethyl methacrylate and 87 mL of γ-butyrolactone. While stirring at room temperature, 16.22 g (0.21 mol) of pyridine was added to obtain the reaction mixture. After the exothermic reaction was complete, the mixture was allowed to cool to room temperature and stand for 16 hours.

[0225] Next, while stirring under ice-cold conditions, a solution of 41.27 g (0.2 mol) of dicyclohexylcarbodiimide (DCC) dissolved in 40 mL of γ-butyrolactone was added to the reaction mixture over 20 minutes. Then, while stirring, a substance obtained by suspending 23.44 g (0.064 mol) of BAHF and 7.75 g (0.016 mol) of monomer in 100 mL of γ-butyrolactone was added over 20 minutes. Further, after stirring at room temperature for 2 hours, 4.36 g (0.040 mol) of 3-aminophenol was added, and stirring was continued for 1 hour. Then, 65 mL of γ-butyrolactone was added. The precipitate formed in the reaction mixture was removed by filtration to obtain the reaction solution.

[0226] The resulting reaction solution was added to 800 mL of ethanol, generating a precipitate containing crude polymer. The crude polymer was filtered off and dissolved in 300 mL of tetrahydrofuran to obtain a crude polymer solution. The obtained crude polymer solution was added dropwise to 6 L of water to precipitate the polymer. The precipitate was collected by filtration, washed three times with water, and then vacuum dried to obtain a powdered polyimide precursor (A-35).

[0227] <Synthesis Example 36: Synthesis of Polyimide (A-36)> Under a dry nitrogen stream, 1.02 g (0.100 mol) of ODPA was dissolved in 234.67 g of NMP at 60 °C. Then, 3.27 g (0.030 mol) of MAP was added together with 5 g of NMP, and the reaction was carried out at 60 °C for 15 minutes. Subsequently, 23.44 g (0.064 mol) of BAHF, 7.75 g (0.016 mol) of monomer X, 1.24 g (0.005 mol) of SiDA, and 20 g of NMP were added together, and the reaction was carried out at 60 °C for 2 hours. Next, the temperature was raised to 200 °C, and the reaction was carried out for 3 hours. After cooling to 40 °C, 19.86 g (0.128 mol) of CARENZ MOI was added together with 49.65 g of NMP under a compressed air stream, and the reaction was carried out at 40 °C for 2 hours. After the reaction was complete, the solution was cooled to room temperature and added to 3 L of water, yielding a white precipitate. The precipitate was collected by filtration, washed three times with water, and then dried in a ventilated dryer at 50°C for three days to obtain polyimide (A-36) powder.

[0228] <Synthesis Example 37: Synthesis of Polyimide (A-37)> Under a dry nitrogen stream, 29.30 g (0.08 mol) of BAHF, 1.24 g (0.005 mol) of SiDA, and 3.27 g (0.03 mol) of 3-aminophenol were dissolved in 180 g of NMP. Then, 1.02 g (0.1 mol) of ODPA and 20 g of NMP were added together, and the mixture was reacted at 60 °C for 1 hour, followed by stirring at 180 °C for 4 hours. After stirring, the solution was added to 3 L of water, yielding a white precipitate. The precipitate was collected by filtration, washed three times with water, and dried in a vacuum dryer at 80 °C for 20 hours to obtain polyimide (A-37) powder.

[0229] <Synthesis Example 38: Synthesis of Polyimide (A-38)> Under a dry nitrogen stream, 29.30 g (0.072 mol) of BAHF, 1.60 g (0.008 mol) of 1,12-diaminododecane, 1.24 g (0.005 mol) of SiDA, and 3.27 g (0.03 mol) of 3-aminophenol were dissolved in 80 g of NMP. Then, 1.02 g (0.1 mol) of ODPA and 20 g of NMP were added together, and the mixture was reacted at 60 °C for 1 hour, followed by stirring at 180 °C for 4 hours. After stirring, the solution was added to 3 L of water, yielding a white precipitate. The precipitate was collected by filtration, washed three times with water, and dried in a vacuum dryer at 80 °C for 20 hours to obtain polyimide (A-38) powder.

[0230] <Synthesis Example 39: Synthesis of Polyimide (A-39)> Under a dry nitrogen stream, 29.30 g (0.072 mol) of BAHF, 7.20 g (0.008 mol) of ED-900 (manufactured by HUNTSMAN), 1.24 g (0.005 mol) of SiDA, and 3.27 g (0.03 mol) of 3-aminophenol were dissolved in 180 g of NMP. Then, 31.02 g (0.1 mol) of ODPA was added together with 20 g of NMP, and the mixture was reacted at 60 °C for 1 hour, followed by stirring at 180 °C for 4 hours. After stirring, the solution was added to 3 L of water, yielding a white precipitate. The precipitate was collected by filtration, washed three times with water, and dried in a vacuum dryer at 80 °C for 20 hours to obtain polyimide (A-39) powder.

[0231] <Synthetic Example 40: Synthesis of Polyimide Precursor (A-40)> Under a dry nitrogen stream, 6.20 g (0.02 mol) of ODPA was dissolved in 100 g of NMP. Then, 5.27 g (0.016 mol) of BAHF was added together with 25 g of NMP, and the reaction was carried out at 20 °C for 1 hour, followed by a reaction at 50 °C for 2 hours. Next, 0.87 g (0.008 mol) of 3-aminophenol was added, and the reaction was carried out at 50 °C for 2 hours. Subsequently, a solution obtained by diluting 7.15 g (0.06 mol) of DFA with 10 g of NMP was added dropwise over 10 minutes. After the addition, the mixture was stirred at 50 °C for 3 hours. After the reaction was complete, the solution was added to 1 L of water, and the polymer solid precipitate was collected by filtration. The polymer solid was dried in a vacuum dryer at 80 °C for 20 hours to obtain polymer (A-40) (polyamic acid ester).

[0232] <Synthetic Example 41: Synthesis of Polyhydroxyamide (A-41)> Under a dry nitrogen stream, 100 g of NMP was added, along with BAHF (16.48 g, 0.045 mol) and 3-aminophenol (1.09 g, 0.010 mol). After dissolving by stirring at room temperature, the reaction solution was maintained at -10 to 0 °C. Simultaneously, 4,4′-diphenyl ether dicarboxylic acid chloride (14.76 g, 0.05 mol) was added, and the mixture was stirred continuously at room temperature for 3 hours. The reaction solution was then added to 3 liters of water, and the precipitate was recovered. After washing three times with pure water, the precipitate was dried in a vacuum dryer at 80 °C for 20 hours to obtain polyhydroxyamide (A-41) powder.

[0233] <Synthetic Example 42: Synthesis of Polyhydroxyamide (A-42)> Under a dry nitrogen stream, 100 g of NMP was added, along with BAHF (14.83 g, 0.0405 mol), 1,12-diaminododecane (0.90 g, 0.0045 mol), and 3-aminophenol (1.09 g, 0.010 mol). After dissolving by stirring at room temperature, the reaction solution was kept at -10 to 0 °C. Simultaneously, 4,4′-diphenyl ether dicarboxylic acid chloride (14.76 g, 0.05 mol) was added, and the mixture was stirred continuously at room temperature for 3 hours. The reaction solution was then added to 3 liters of water, and the precipitate was recovered. After washing three times with pure water, the precipitate was dried in a vacuum dryer at 80 °C for 20 hours to obtain polyhydroxyamide (A-42) powder.

[0234] <Synthetic Example 43: Synthesis of Polyhydroxyamide (A-43)> Under a dry nitrogen stream, 100 g of NMP was added, along with BAHF (14.83 g, 0.0405 mol), ED-900 (4.05 g, 0.0045 mol), and 3-aminophenol (1.09 g, 0.010 mol). After dissolving by stirring at room temperature, the reaction solution was kept at -10 to 0 °C. Simultaneously, 4,4′-diphenyl ether dicarboxylic acid chloride (14.76 g, 0.05 mol) was added, and the mixture was stirred continuously at room temperature for 3 hours. The reaction solution was then added to 3 liters of water, and the precipitate was recovered. After washing three times with pure water, the precipitate was dried in a vacuum dryer at 80 °C for 20 hours to obtain polyhydroxyamide (A-43) powder.

[0235] <Synthetic Example 44: Synthesis of Polyhydroxyamide (A-44)> Under a dry nitrogen stream, 100 g of NMP was added, along with BAHF (32.96 g, 0.090 mol) and m-aminophenol (2.18 g, 0.020 mol). After dissolving by stirring at room temperature, the reaction solution was kept at -10 to 0 °C while dodecanoic acid chloride (20.04 g, 0.075 mol) was added dropwise over 10 minutes. Then, 4,4′-diphenyl ether dicarboxylic acid chloride (7.38 g, 0.025 mol) was added, and the mixture was stirred continuously at room temperature for 3 hours. The reaction solution was then added to 3 liters of water, and the precipitate was recovered. After washing three times with pure water, the precipitate was dried in a vacuum dryer at 80 °C for 20 hours to obtain polyhydroxyamide (A-44) powder.

[0236] <Synthetic Example 45: Synthesis of Polyimide Precursor (A-45)> 31.02 g (0.10 mol) of ODPA was added to a 500 mL separable flask, along with 26.03 g (0.20 mol) of 2-hydroxyethyl methacrylate and 87 mL of γ-butyrolactone. While stirring at room temperature, 16.22 g (0.21 mol) of pyridine was added to obtain the reaction mixture. After the exothermic reaction was complete, the mixture was allowed to cool to room temperature and stand for 16 hours.

[0237] Next, under ice-cooled conditions, while stirring, a solution of 41.27 g (0.2 mol) of dicyclohexylcarbodiimide (DCC) dissolved in 40 mL of γ-butyrolactone was added to the reaction mixture over 20 minutes. Then, while stirring, a substance obtained by suspending 23.44 g (0.064 mol) of BAHF and 3.20 g (0.016 mol) of 1,12-diaminododecane in 100 mL of γ-butyrolactone was added over 20 minutes. Further, after stirring at room temperature for 2 hours, 4.36 g (0.040 mol) of 3-aminophenol was added, and stirring was continued for 1 hour. Then, 65 mL of γ-butyrolactone was added. The precipitate formed in the reaction mixture was removed by filtration to obtain the reaction solution.

[0238] The resulting reaction solution was added to 800 mL of ethanol, generating a precipitate containing crude polymer. The crude polymer was filtered off and dissolved in 300 mL of tetrahydrofuran to obtain a crude polymer solution. The obtained crude polymer solution was added dropwise to 6 L of water to precipitate the polymer. The precipitate was collected by filtration, washed three times with water, and then dried under vacuum to obtain a powdered polyimide precursor (A-45).

[0239] <Synthetic Example 46: Synthesis of Polyimide (A-46)> Under a dry nitrogen stream, 1.02 g (0.100 mol) of ODPA was dissolved in 234.67 g of NMP at 60 °C. Then, 3.27 g (0.030 mol) of MAP was added together with 5 g of NMP, and the reaction was carried out at 60 °C for 15 minutes. Subsequently, 23.44 g (0.064 mol) of BAHF, 3.20 g (0.016 mol) of 1,12-diaminododecane, 1.24 g (0.005 mol) of SiDA, and 20 g of NMP were added together, and the reaction was carried out at 60 °C for 2 hours. Next, the temperature was raised to 200 °C, and the reaction was carried out for 3 hours. Afterward, the temperature was cooled to 40 °C, and under a compressed air stream, 19.86 g (0.128 mol) of CARENZ MOI and 49.65 g of NMP were added together, and the reaction was carried out at 40 °C for 2 hours. After the reaction was completed, the solution was cooled to room temperature and then added to 3 L of water, resulting in a white precipitate. The precipitate was collected by filtration, washed three times with water, and then dried in a ventilated dryer at 50 °C for three days to obtain polyimide (A-46) powder.

[0240] [Examples 1-46, Comparative Examples 1-16] To prepare a varnish, add 10g of component (A), components (B), (C), (D), and γ-butyrolactone as component (E).

[0241] The components (B-1) (manufactured by Daito-Kemitz Co., Ltd.), (B-2) (manufactured by BASF Co., Ltd.), (C-1) (manufactured by Gunei Chemical Industry Co., Ltd.), (C-2) and (D) (manufactured by DIC Co., Ltd.) used in the examples are as follows.

[0242] [Chemistry 18]

[0243] The characteristic results of the resin compositions obtained in each embodiment and comparative example are shown in Tables 1 and 2.

[0244]

[0245] [Table 2] Industrial utilization potential

[0246] The resin composition of the present invention can be suitably used in surface protective films for semiconductor elements, interlayer insulating films, insulating layers for display devices such as organic light-emitting elements, planarization films for thin film transistor (TFT) substrates, wiring protective insulating films for circuit boards, on-chip microlenses for solid-state imaging elements, planarization films for various displays and solid-state imaging elements, and solder resists for circuit boards. Marker description

[0247] 1a Cross-section view 1b (Image above) 11 Antenna Section 12 Matching Circuit 13 MSL power supply lines 14 Power Supply Points 15 Ground wire 16 Insulating film J Ground wire wiring thickness K antenna wiring thickness L Antenna length M Matching circuit length W antenna width 201 IC Chip 202 Electrode Pad 203 Second via routing 204 Planar Antenna Wiring 205 Second sealing resin 206 Ground wire wiring 207 First via routing 208 First sealing resin 209 Copper Wiring 210 Insulating film 211 Barrier Metal 212 Solder bump

Claims

1. A resin composition comprising (A) a resin and (E) a solvent, wherein the resin (A) comprises at least one selected from polyimide, polyamide, polybenzoxazole, precursors thereof, and copolymers thereof, and the resin (A) has the structure shown in formula (1). [Chemistry 1] In equation (1), a is an integer from 1 to 4, b is an integer from 1 to 2, and n is an integer from 1 to 12; A is a single bond, -O-, -S-, -CO-, -COO-, -OCO-, -NHCO-, -CONH-, or a divalent hydrocarbon group with 1 to 5 carbon atoms, and R 1 Each is independently a halogen atom, a hydroxyl group, a monovalent hydrocarbon group with 1 to 6 carbon atoms, an alkoxy group with 1 to 6 carbon atoms, or a phenoxy group, and R 1 One or two of them are hydroxyl groups; * indicates a chemical bond.

2. A resin composition comprising (A) a resin and (E) a solvent, wherein the (A) resin comprises at least one selected from polyimide, polyamide, polybenzoxazole, precursors thereof, and copolymers thereof, the (A) resin having the structure shown in formula (1), the (A) resin having one or more structural units selected from structural units shown in formula (2), formula (3), and formula (4), wherein the total content of the structural units shown in formula (2), formula (3), and formula (4) is 10 mol% or more and 20 mol% or less in 100 mol% of the total structural units of the (A) resin. [Chemistry 2] In equation (1), a is an integer from 0 to 4, b is an integer from 0 to 2, and when b is 0, the part in parentheses represents a single bond; n is an integer from 1 to 12; A is an integer from 0 to 2, -O-, -S-, -CO-, -COO-, -OCO-, -NHCO-, -CONH-, or a divalent hydrocarbon group with 1 to 5 carbon atoms; R 1 Each is independently a halogen atom, a monovalent hydrocarbon group with 1 to 6 carbon atoms, an alkoxy group with 1 to 6 carbon atoms, or a phenoxy group; * indicates a chemical bond; [Chemistry 3] In equation (2), R 2 R represents a tetravalent organic group with 4 to 40 carbon atoms; 3 The structure representing the case where b is 1 or 2 in the structure shown in the aforementioned equation (1); [Chemistry 4] In equation (3), R 4 R represents an organic group with 4 to 40 carbon atoms and a 2 to 8 valence. 5 This represents the structure shown in equation (1) above, where b is 1 or 2; R 6 This represents a monovalent hydrocarbon group with 1 to 20 hydrogen or carbon atoms; q and r represent integers within the range of 0 ≤ q ≤ 4 and 0 ≤ r ≤ 4; when q and r are 0, (OH) q (COOR) 6 ) r q represents a hydrogen atom; r represents integers that satisfy 0 ≤ q + r ≤ 6; [Chemistry 5] In equation (4), R 7 R represents the structural unit in the structure shown in equation (1) where b is 0; 8 It represents a divalent organic group with 4 to 40 carbon atoms.

3. The resin composition according to claim 1 or 2, wherein, The aforementioned (A) resin is (a-1) an alkali-soluble resin, and the resin composition further contains (B-1) a compound that generates acid through light and (C-1) a thermal crosslinking agent.

4. The resin composition according to claim 1 or 2, further comprising (B-2) a photopolymerization initiator and (C-2) a compound having two or more olefinic unsaturated bonds.

5. The resin composition according to claim 1 or 2, further comprising (B-2) a photopolymerization initiator, wherein the aforementioned (A) resin has olefinic unsaturated bonds.

6. The resin composition according to claim 5, wherein, In the aforementioned equation (1), b is 1.

7. The resin composition according to claim 1, wherein, The aforementioned resin (A) has one or more structural units selected from the structural units shown in formula (2), formula (3), and formula (4), wherein the total content of the structural units shown in formula (2), formula (3), and formula (4) in the total structural units of resin (A) is 10 mol% or more and 100 mol% or less. [Chemistry 7] In equation (2), R 2 R represents a tetravalent organic group with 4 to 40 carbon atoms; 3 The structure representing the case where b is 1 or 2 in the structure shown in the aforementioned equation (1); [Chemistry 8] In equation (3), R 4 R represents an organic group with 4 to 40 carbon atoms and a 2 to 8 valence. 5 This represents the structure shown in equation (1) above, where b is 1 or 2; R 6 This represents a monovalent hydrocarbon group with 1 to 20 hydrogen or carbon atoms; q and r represent integers within the range of 0 ≤ q ≤ 4 and 0 ≤ r ≤ 4; when q and r are 0, (OH) q (COOR) 6 ) r q represents a hydrogen atom; r represents integers that satisfy 0 ≤ q + r ≤ 6; [Chemistry 9] In equation (4), R 7 R represents the structural unit in the structure shown in equation (1) where b is 0; 8 It represents a divalent organic group with 4 to 40 carbon atoms.

8. The resin composition according to claim 1 or 2, further comprising the compound shown in formula (D) (5), [Chemistry 10] In equation (5), R 9 R represents an alkyl group with 1 or more but less than 15 carbon atoms. 10 Indicates an alkylene group having 2 or more but less than 10 carbon atoms; R 11 It represents an alkyl group with 1 or more but less than 20 carbon atoms, an alkylene group with 1 or more but less than 20 carbon atoms, or a 1 to 20 valent organic group containing at least one of O, S and N atoms; k represents an integer from 1 to 4.

9. The resin composition according to claim 1 or 2, wherein, The aforementioned resin (A) has the structure shown in formula (6) and / or the structure shown in formula (7). [Chemistry 11] In equation (6), R 16 and R 17 Each represents a monovalent organic group or hydroxyl group with 1 to 5 carbon atoms, v and w each represent integers from 0 to 4, m represents integers from 0 to 2, and * represents a chemical bond; except for those included in the structural unit shown in formula (1); [Chemistry 12] In equation (7), R 18 and R 19 Each represents a monovalent organic group or hydroxyl group with 1 to 5 carbon atoms, x and y represent integers from 0 to 4, and * represents a chemical bond.

10. A cured film, which is formed by curing the resin composition according to any one of claims 1 to 9.

11. A cured film having (A) resin, (A) resin comprising at least one selected from polyimide, polyamide, polybenzoxazole, precursors thereof and copolymers thereof, (A) resin having the structure shown in formula (1), [Chemistry 13] In equation (1), a is an integer from 1 to 4, b is an integer from 1 to 2, and n is an integer from 1 to 12; A is a single bond, -O-, -S-, -CO-, -COO-, -OCO-, -NHCO-, -CONH-, or a divalent hydrocarbon group with 1 to 5 carbon atoms, and R 1 Each is independently a halogen atom, a hydroxyl group, a monovalent hydrocarbon group with 1 to 6 carbon atoms, an alkoxy group with 1 to 6 carbon atoms, or a phenoxy group, and R 1 One or two of them are hydroxyl groups; * indicates a chemical bond.

12. A cured film having (A) resin, (A) resin comprising at least one selected from polyimide, polyamide, polybenzoxazole, precursors thereof and copolymers thereof, (A) resin having the structure shown in formula (1), wherein the aforementioned (A) resin has one or more structural units selected from the structural units shown in formula (2), formula (3) and formula (4), wherein the total content of the aforementioned structural units shown in formula (2), formula (3) and formula (4) is 10 mol% or more and 20 mol% or less in 100 mol% of the structural units of the total (A) resin. [Chemistry 14] In equation (1), a is an integer from 0 to 4, b is an integer from 0 to 2, and when b is 0, the part in parentheses represents a single bond; n is an integer from 1 to 12; A is an integer from 0 to 2, -O-, -S-, -CO-, -COO-, -OCO-, -NHCO-, -CONH-, or a divalent hydrocarbon group with 1 to 5 carbon atoms; R 1 Each is independently a halogen atom, a monovalent hydrocarbon group with 1 to 6 carbon atoms, an alkoxy group with 1 to 6 carbon atoms, or a phenoxy group; * indicates a chemical bond; [Chemistry 15] In equation (2), R 2 R represents a tetravalent organic group with 4 to 40 carbon atoms; 3 The structure representing the case where b is 1 or 2 in the structure shown in the aforementioned equation (1); [Chemistry 16] In equation (3), R 4 R represents an organic group with 4 to 40 carbon atoms and a 2 to 8 valence. 5 This represents the structure shown in equation (1) above, where b is 1 or 2; R 6 This represents a monovalent hydrocarbon group with 1 to 20 hydrogen or carbon atoms; q and r represent integers within the range of 0 ≤ q ≤ 4 and 0 ≤ r ≤ 4; when q and r are 0, (OH) q (COOR) 6 ) r q represents a hydrogen atom; r represents integers that satisfy 0 ≤ q + r ≤ 6; [Chemistry 17] In equation (4), R 7 R represents the structural unit in the structure shown in equation (1) where b is 0; 8 It represents a divalent organic group with 4 to 40 carbon atoms.

13. An insulating or protective film having a cured film as described in any one of claims 10 to 12.

14. A method for manufacturing an electronic component, display device, or semiconductor device, comprising: The step of coating the resin composition according to any one of claims 1 to 9 and drying it to form a resin film; The step of irradiating the resin film with chemical rays; The steps of developing a resin film to form a pattern; and the steps of heat treatment to form a textured pattern layer of a cured film.

15. An electronic component, display device, or semiconductor device having a textured layer of the cured film according to any one of claims 10 to 12.

16. An electronic component, display device, or semiconductor device, wherein the cured film of any one of claims 10 to 12 is configured as an insulating film between wirings.

17. An antenna element having at least one antenna wiring and a cured film according to any one of claims 10 to 12, wherein the antenna wiring comprises at least one selected from a bent loop antenna, a coil loop antenna, a bent monopole antenna, a bent dipole antenna, and a microstrip antenna, and wherein the proprietary area of ​​an average antenna portion in the antenna wiring is 1000 mm². 2 The cured film is described below as an insulating film that insulates the ground wire and the antenna wiring.

18. The electronic component of claim 16, comprising at least a semiconductor package having a semiconductor element, a redistribution layer, a sealing resin, and an antenna wiring, wherein the insulating layer of the redistribution layer and / or the sealing resin comprises the aforementioned cured film, the sealing resin being disposed between the ground wire and the antenna wiring.

19. The electronic component according to claim 18, comprising an antenna element obtained by laminating an antenna wiring and the aforementioned cured film, wherein the height of the antenna wiring is 50 to 200 μm and the thickness of the cured film is 80 to 300 μm.

Citation Information

Patent Citations

  • Photosensitive resin composition, method for producing patterned cured film using the same and electronic component

    JP2008224984A

  • Positive photosensitive resin composition

    JP2011197362A

  • Resin composition, resin sheet, cured film, production method of cured film, semiconductor device and display device

    JP2020066651A

  • Low dielectric constant film and semiconductor device

    JP2001237241A

  • Photosensitive polyimide precursor composition and metal foil-polyimide composite

    JP2001254014A